Battery cell, battery device, and electric device

CN123018149APending Publication Date: 2026-10-30CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510553716.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2026-10-30

Smart Images

  • Figure CN123018149A_ABST
    Figure CN123018149A_ABST
Patent Text Reader

Abstract

The application provides a battery monomer, a battery device and a power utilization device. The battery monomer comprises an electrode assembly and an electrolyte. The electrode assembly comprises a positive electrode sheet, a separator and a negative electrode sheet. The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer arranged on at least one side of the positive electrode current collector. The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer arranged on at least one side of the negative electrode current collector. The positive electrode active material layer comprises a lithium-containing phosphate with an olivine structure. The negative electrode active material layer comprises a linear polymer alkali metal salt, a silicon-based material and a carbon-based material. The mass content of the linear polymer alkali metal salt in the negative electrode active material layer is 0.3% to 2%. The mass content of silicon in the silicon-based material in the negative electrode active material layer is 0.5% to 5%. The application can balance the energy density, the rapid charging performance and the cycle performance of the battery monomer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a battery cell, a battery device, and an electrical device. Background Technology

[0002] Battery cells have characteristics such as high capacity and long lifespan, and are therefore widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric cars, electric airplanes, electric ships, and power tools.

[0003] With the development of lithium-ion battery applications, higher requirements have been placed on the performance of individual battery cells, such as energy density, fast charging performance, and cycle performance. However, related technologies cannot simultaneously achieve the desired energy density, fast charging performance, and cycle performance of individual battery cells. Summary of the Invention

[0004] This application provides a battery cell, a battery device, and an electrical device that can balance the energy density, fast charging performance, and cycle performance of the battery cell.

[0005] In a first aspect, this application proposes a battery cell, which includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode, a separator, and a negative electrode. The positive electrode includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector. The negative electrode includes a negative current collector and a negative active material layer disposed on at least one side of the negative current collector.

[0006] The positive electrode active material layer includes lithium phosphate with an olivine structure;

[0007] The negative electrode active material layer includes linear polymer alkali metal salt, silicon-based material and carbon-based material. The mass content of linear polymer alkali metal salt in the negative electrode active material layer is 0.3% to 2%, and the mass content of silicon element in silicon-based material in the negative electrode active material layer is 0.5% to 5%.

[0008] In this embodiment, by limiting the mass content of silicon within an appropriate range, the volumetric energy density of the battery cell is improved, while reducing the volume expansion problem that may be caused by excessive silicon-based material. An appropriate amount of linear polymer alkali metal salt is added to the negative electrode active material layer. Its adhesiveness effectively binds the particles in the negative electrode active material layer, alleviating the volume expansion of the silicon-based material during charging and discharging. Its linear main chain structure tightly encapsulates the silicon-based material, reducing the adverse effects of volume expansion on the solid electrolyte interphase (SEI) film. By reasonably controlling the amount of linear polymer alkali metal salt, while improving the volume expansion of the silicon-based material, its adhesiveness does not significantly affect the kinetic performance of the battery cell, and it does not significantly reduce the capacity of the negative electrode. Furthermore, although the kinetic performance of the silicon-based material itself is poor, the alkali metal ions of the linear polymer alkali metal salt can provide additional alkali metal ions to the negative electrode active material layer, improving the ion transport rate, thereby enhancing the kinetic performance of the battery cell and improving fast charging performance. In summary, the battery cell can achieve a balance of high energy density, excellent cycle performance, and fast charging performance.

[0009] In some embodiments, the mass content of the linear polymer alkali metal salt in the negative electrode active material layer is 0.5% to 2%, optionally 0.7% to 1.3%. When the mass content of the linear polymer alkali metal salt is within the above range, the encapsulation effect on the silicon-based material is better, which is more conducive to balancing the energy density, cycle performance and fast charging performance of the battery cell.

[0010] In some embodiments, the alkali metal element in the linear polymer alkali metal salt has a mass content of 3% to 7.5%. When the mass content of the alkali metal element is within the above range, the number of freely moving alkali metal ions in the negative electrode active material layer is relatively large, which can further shorten the distance of alkali metal ions to diffuse to the surface of the negative electrode active material layer, improve the deintercalation rate of alkali metal ions, and improve the fast charging performance of the battery cell.

[0011] In some embodiments, the alkali metal element of the linear polymer alkali metal salt includes one or more elements such as lithium, sodium, and potassium. The aforementioned material can provide alkali metal ions, improve the kinetic performance of the negative electrode active material layer, and enhance the fast-charging performance of the battery cell.

[0012] In some embodiments, the number-average molecular weight of the linear polymer alkali metal salt is between 3 kDa and 1000 kDa. When the number-average molecular weight of the linear polymer alkali metal salt is within the above range, the linear polymer alkali metal salt has an appropriate viscosity, which on the one hand can increase the compactness of each particle in the negative electrode active material layer and reduce the contact internal resistance, and on the other hand can effectively encapsulate the silicon-based material, alleviate the volume expansion of the silicon-based material, and improve the cycle performance and fast charging performance of the battery cell.

[0013] In some embodiments, the polydispersity index of the linear polymer alkali metal salt is between 1 and 1.5. When the polydispersity index of the linear polymer alkali metal salt is within the above range, the molecular weight distribution of the linear polymer alkali metal salt is more concentrated, the performance of the linear polymer alkali metal salt is more uniform, and it can more effectively improve the performance of the negative electrode active material layer, which is beneficial to improving the cycle performance and fast charging performance of the battery cell.

[0014] In some embodiments, the linear polymer alkali metal salt includes one or more of polyacrylate alkali metal salts and polymethacrylate alkali metal salts. These materials provide superior encapsulation of silicon-based materials, which is more conducive to balancing the energy density, cycle performance, and fast charging performance of individual battery cells.

[0015] In some embodiments, the negative electrode active material layer further includes a negative electrode binder, which includes one or more of styrene-butadiene rubber, water-soluble unsaturated resin, water-based acrylic resin, polyvinyl alcohol, sodium alginate, and carboxymethyl chitosan. The negative electrode binder can improve the bonding force between the negative electrode active material layer and the negative electrode current collector, enhance the structural stability of the negative electrode sheet, and improve the cycle performance of the battery cell.

[0016] In some embodiments, the mass content of the negative electrode binder in the negative electrode active material layer is 0.5% to 3.5%. When the mass content of the negative electrode binder is within the above range, both the energy density and cycle performance of the battery cell can be balanced.

[0017] In some embodiments, the negative electrode active material layer further includes carbon nanotubes, with the carbon nanotubes comprising 0.01% to 1% by mass. On the one hand, carbon nanotubes can improve the conductivity of the negative electrode sheet; on the other hand, their linear structure allows them to wrap around the surface of the silicon-based material, mitigating the volume expansion of the silicon-based material and improving the fast-charging performance and cycle performance of the battery cell.

[0018] In some embodiments, the length of the carbon nanotubes is 1 μm to 5 μm; carbon nanotubes of this size can improve both the fast charging performance and cycle performance of the battery cell.

[0019] In some embodiments, carbon nanotubes include one or more types of single-walled carbon nanotubes and multi-walled carbon nanotubes. Carbon nanotubes of the above materials can improve both the fast-charging performance and cycle performance of individual battery cells.

[0020] In some embodiments, the silicon content of the silicon element in the negative electrode active material layer is between 0.7% and 3.5% by mass. When the silicon content in the negative electrode active material layer meets the above range, the capacity of the negative electrode active material layer can be increased, thereby improving the energy density of the battery cell.

[0021] In some embodiments, the silicon-based material includes one or more of elemental silicon, silicon-carbon materials, silicon-oxygen materials, silicon-nitrogen materials, and silicon alloys. These materials have high specific capacity, which is beneficial for improving the energy density of individual battery cells.

[0022] In some embodiments, the silicon-based material includes one or more of silicon-carbon materials, silicon-oxygen materials, silicon-nitrogen materials, and silicon alloys. These materials have high specific capacity, which is beneficial for improving the energy density of individual battery cells.

[0023] In some implementations, the silicon content is 40% to 80% based on the total mass of the silicon-based material; when the silicon-based material meets the above conditions, it is beneficial to balance the energy density, fast charging performance and cycle performance of the battery cell.

[0024] In some embodiments, the volume average particle size Dv50 of the silicon-based material is 3.0 μm to 10 μm; when the silicon-based material meets the above conditions, it is beneficial to balance the energy density, fast charging performance and cycle performance of the battery cell.

[0025] In some implementations, the specific surface area of ​​the silicon-based material is 1 m². 2 / g to 3.6m 2 / g; When silicon-based materials meet the above conditions, they are beneficial to balance the energy density, fast charging performance and cycle performance of battery cells.

[0026] In some embodiments, the powder compaction density of the silicon-based material at 25000 N is 0.7 g / cm³. 3 Up to 1.2 g / cm 3 When silicon-based materials meet the above conditions, they are beneficial for balancing the energy density, fast charging performance, and cycle performance of individual battery cells.

[0027] In some embodiments, the carbon-based material includes graphite bulk particles and a negative electrode coating layer covering the surface of the graphite bulk particles. The graphite bulk particles include secondary particles, and the negative electrode coating layer includes carbon elements. The carbon elements in the negative electrode coating layer can improve the fast charging performance of the battery cell.

[0028] In some embodiments, the graphite bulk particles include at least one of synthetic graphite and natural graphite. Synthetic graphite exhibits superior cycle performance, which is beneficial for improving the cycle performance of individual battery cells.

[0029] In some embodiments, based on the total mass of carbon-based materials, the carbon content of the negative electrode coating is 2% to 5% by mass. When the carbon content of the negative electrode coating is within the above range, the internal resistance of the negative electrode sheet can be further reduced, which can improve the fast charging performance of the battery cell. With a smaller internal resistance, the heat generated inside the battery cell is reduced, which is beneficial to improving the stability of the electrolyte and improving the cycle performance of the battery cell.

[0030] In some embodiments, the negative electrode active material layer includes a first negative electrode active material layer and a second negative electrode active material layer. The first negative electrode active material layer is disposed on the negative electrode current collector; the second negative electrode active material layer is disposed on the side of the first negative electrode active material layer away from the negative electrode current collector. Both the first and second negative electrode active material layers comprise carbon-based materials, and at least one of the first and second negative electrode active material layers comprises a silicon-based material. The negative electrode active material layer includes at least two film layers, which is beneficial for balancing the fast charging performance and energy density of the battery cell.

[0031] In some embodiments, the volume average particle size Dv50 of the carbon-based material in the first negative electrode active material layer is greater than or equal to the volume average particle size Dv50 of the carbon-based material in the second negative electrode active material layer. This difference in particle size between the first and second negative electrode active material layers can improve the fast-charging performance of the battery cell.

[0032] In some embodiments, the volume average particle size Dv50 of the carbon-based material in the first negative electrode active material layer is 10 μm to 20 μm. When the volume average particle size Dv50 of the carbon-based material is within the above range, it is possible to balance the fast charging performance and cycle performance of the battery cell.

[0033] In some embodiments, the volume average particle size Dv50 of the carbon-based material in the second negative electrode active material layer is between 9.5 μm and 14.5 μm. When the volume average particle size Dv50 of the carbon-based material is within the above range, it is possible to balance the fast charging performance and cycle performance of the battery cell.

[0034] In some embodiments, the mass content of the linear polymer alkali metal salt in the first negative electrode active material layer is greater than or equal to the mass content of the linear polymer alkali metal salt in the second negative electrode active material layer.

[0035] The linear polymer alkali metal salt has a relatively high mass content in the first negative electrode active material layer. The linear polymer alkali metal salt provides the first negative electrode active material layer with a relatively larger number of freely mobile alkali metal ions, such as lithium ions, which can further improve the fast charging performance of the battery cell.

[0036] In some embodiments, the linear polymer alkali metal salt in the first negative electrode active material layer has a mass content of 0.3% to 2.5%; the lithium element in the linear polymer alkali metal salt can exist in ionic form, which can increase the number of freely moving alkali metal ions, such as lithium ions, in the negative electrode active material layer, shorten the distance for lithium ions to diffuse to the surface of the negative electrode active material layer, improve the lithium ion insertion / extraction rate, and improve the fast charging performance of the battery cell.

[0037] In some embodiments, the linear polymer alkali metal salt in the second negative electrode active material layer has a mass content of 0.2% to 1.5%. The lithium element in the linear polymer alkali metal salt can exist in ionic form, which can increase the number of freely moving alkali metal ions, such as lithium ions, in the negative electrode active material layer, shorten the distance that lithium ions diffuse to the surface of the negative electrode active material layer, increase the lithium ion insertion / extraction rate, and improve the fast charging performance of the battery cell.

[0038] In some embodiments, the linear polymer alkali metal salt of the first negative electrode active material layer has a mass content of A1% in the first negative electrode active material layer; the first negative electrode active material layer includes a negative electrode binder, which includes one or more of styrene-butadiene rubber, water-soluble unsaturated resin, water-based acrylic resin, polyvinyl alcohol, sodium alginate, and carboxymethyl chitosan, and the mass content of the negative electrode binder of the first negative electrode active material layer is B1%; the linear polymer alkali metal salt of the second negative electrode active material layer has a mass content of A2% in the second negative electrode active material layer; the second negative electrode active material layer includes a negative electrode binder, which includes one or more of styrene-butadiene rubber, water-soluble unsaturated resin, water-based acrylic resin, polyvinyl alcohol, sodium alginate, and carboxymethyl chitosan, and the mass content of the negative electrode binder of the second negative electrode active material layer is B2%, and A1% + B1% ≥ A2% + B2%.

[0039] The high total mass content of the linear polymer alkali metal salt and negative electrode binder in the first negative electrode active material layer results in a strong bond between the negative electrode active material layer and the negative electrode current collector. During the cycle of the battery cell, the negative electrode sheet exhibits excellent cycle stability, which is beneficial for improving the cycle performance of the battery cell.

[0040] In some embodiments, A1% + B1% is 0.5% to 3.5%; and / or A2% + B2% is 0.5% to 2.5%. When the negative electrode active material layer meets the above conditions, it is beneficial to improve both the cycle performance and energy density of the battery cell.

[0041] In some embodiments, the thickness ratio of the first negative electrode active material layer to the second negative electrode active material layer is 2:8 to 6:4, and optionally 3:7 to 5:5. A thickness ratio within the above range can further increase the gradient porosity difference between the upper and lower layers, reduce lithium-ion transport tortuosity, and improve the fast-charging capability of the battery cell.

[0042] In some embodiments, the negative electrode sheet further includes a negative electrode conductive layer, which is located between the negative electrode current collector and the negative electrode active material layer. The negative electrode conductive layer can further improve the conductivity of the negative electrode sheet and improve the fast charging performance of the battery cell.

[0043] In some embodiments, the negative electrode conductive layer includes a negative electrode conductive agent, which includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The negative electrode conductive agent in the negative electrode conductive layer can improve the conductivity of the negative electrode conductive layer, thereby improving the conductivity of the negative electrode sheet and reducing the heat generation of the battery cell. The negative electrode binder in the negative electrode conductive layer can improve the bonding performance between the negative electrode current collector and the negative electrode active material layer, thereby improving the structural stability of the negative electrode sheet.

[0044] In some embodiments, the negative electrode conductive layer includes a negative electrode binder, which includes one or more of styrene-butadiene rubber, water-soluble unsaturated resin, water-based acrylic resin, polyvinyl alcohol, sodium alginate, and carboxymethyl chitosan.

[0045] In some embodiments, the thickness of the negative electrode conductive layer is 0.5 μm to 2 μm. The negative electrode conductive layer can balance the fast charging performance and energy density of the battery cell.

[0046] In some embodiments, the compaction density of the negative electrode active material layer is 1.25 g / cm³. 3 Up to 1.65 g / cm 3 When the compaction density of the negative electrode active material layer is within the above range, it can simultaneously improve the energy density and fast charging performance of the battery cell.

[0047] In some embodiments, the density of the negative electrode active material layer on one side is 80 mg / 1540.25 mm. 2 Up to 160mg / 1540.25mm 2 When the unilateral density of the negative electrode active material layer is within the above range, it is possible to improve both the energy density and fast charging performance of the battery cell.

[0048] In some embodiments, the compaction density of the positive electrode active material layer is 2.60 g / cm³. 3 Up to 2.85 g / cm 3 When the compaction density of the positive electrode active material layer is within the above range, it can simultaneously improve the energy density and fast charging performance of the battery cell.

[0049] In some embodiments, the one-sided surface density of the positive electrode active material layer is 220 mg / 1540.25 mm². 2 Up to 370mg / 1540.25mm 2When the unilateral density of the positive electrode active material layer is within the above range, it is possible to improve both the energy density and fast charging performance of the battery cell.

[0050] In some embodiments, the lithium-containing phosphate includes phosphate particles and a positive electrode coating layer, the positive electrode coating layer being located on at least a portion of the surface of the phosphate particles, and the positive electrode coating layer containing carbon elements. By coating the surface of the phosphate particles with the positive electrode coating layer, the conductivity of the olivine-structured lithium-containing phosphate can be improved, which is beneficial to the migration rate of lithium ions and improves the fast charging performance of the battery cell.

[0051] In some embodiments, the phosphate particles include one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium nickel phosphate, and lithium cobalt phosphate. These materials exhibit excellent cycle stability, which is beneficial for improving the cycle performance of individual battery cells.

[0052] In some embodiments, the battery cell includes an electrolyte, which includes a carbonate additive. The carbonate additive is present in the electrolyte at a mass content of 0.5% to 10%. The carbonate additive includes at least one of vinylene carbonate and ethylene carbonate derivatives, wherein the ethylene carbonate derivatives include compounds represented by Formula A.

[0053]

[0054] In Formula A, Q1, Q2, Q3 and Q4 each independently include any one of a hydrogen atom, a halogen atom, a C1 to C5 alkyl group, or a C1 to C5 haloalkyl group, and at least one of Q1, Q2, Q3 and Q4 includes a halogen atom, a C1 to C5 alkyl group, or a C1 to C5 haloalkyl group.

[0055] Carbonate additives can optimize the composition of the SEI film on the negative electrode side, alleviate the volume expansion of silicon-based materials, and improve the cycle performance and fast charging performance of battery cells.

[0056] In some embodiments, the carbonate additives are present in an amount of 2% to 10% by mass in the electrolyte.

[0057] Carbonate additives can optimize the composition of the SEI film on the negative electrode side, alleviate the volume expansion of silicon-based materials, and improve the cycle performance and fast charging performance of battery cells.

[0058] In some embodiments, the carbonate additives are present in the electrolyte at a mass content of 0.5% to 8%, optionally 1% to 6%. Carbonate additives can optimize the composition of the SEI film on the negative electrode side, alleviate the volume expansion of silicon-based materials, and improve the cycle performance and fast-charging performance of the battery cell.

[0059] In some embodiments, the ethylene carbonate derivative includes one or more of fluoroethylene carbonate, difluoroethylene carbonate, and trifluoromethylethylene carbonate. When the ethylene carbonate derivative includes fluorine atoms, it can form a film rich in F and Li on the negative electrode side. This allows for protection of the negative electrode active material while maintaining low impedance, thus more effectively improving the energy density, fast charging performance, and cycle performance of the battery cell.

[0060] In some embodiments, the electrolyte further includes sulfur-containing additives, including one or more of vinyl sulfate, vinyl disulfate, butene sulfite, 1,3-propanesulfonyl lactone, vinyl sulfite, and methyl methylene disulfonate. The sulfur-containing additives can form a dense SEI film on the negative electrode side, which can effectively mitigate the risk of side reactions between the electrolyte and the negative electrode active material, reduce gas production, and improve the cycle performance of the battery cell.

[0061] In some embodiments, the electrolyte further includes lithium salt additives, including one or more of lithium difluorophosphate, lithium difluorooxalate borate, lithium tetrafluoroborate, and lithium bis(oxalate borate). The lithium salt additives participate in film formation, optimizing the SEI film composition. They also contribute to the formation of an inorganic-rich SEI film, which enhances the high-temperature and high-voltage stability of the SEI film and improves the cycle performance of the battery cells.

[0062] In some embodiments, the sulfur-containing additive is present in the electrolyte at a mass content of 0.3% to 2%. The sulfur-containing additive can improve the cycle performance of the battery cell.

[0063] In some embodiments, the lithium salt additive is present in the electrolyte at a mass content of 0.1% to 3%. The lithium salt additive can improve the cycle performance of the battery cell.

[0064] In some embodiments, the electrolyte includes a carboxylic acid ester solvent, and the mass content of the carboxylic acid ester solvent in the electrolyte is 10% to 60%. When the mass content of the carboxylic acid ester solvent is within the above range, it is beneficial to the migration of lithium ions and can improve the fast charging performance and cycle performance of the battery cell.

[0065] In some embodiments, the carboxylic acid ester solvent includes compounds represented by Formula I.

[0066]

[0067] In formula I,

[0068] R1 includes a hydrogen atom, a C1 to C5 alkyl group, or a C1 to C5 haloalkyl group.

[0069] R2 includes C1 to C5 alkyl or C1 to C5 haloalkyl.

[0070] The aforementioned carboxylic acid ester solvents facilitate lithium ion migration and improve the fast charging capability of individual battery cells.

[0071] In some embodiments, the carboxylic acid ester solvent includes one or more of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, and ethyl butyrate. These carboxylic acid ester solvents facilitate lithium-ion migration and improve the fast-charging capability of individual battery cells.

[0072] In some embodiments, the electrolyte further includes a carbonate solvent, wherein the carbonate solvent comprises 20% to 70% by mass in the electrolyte. This mass content of carbonate solvent can further improve the conductivity of the electrolyte at room temperature, which is beneficial for lithium-ion migration and can improve the fast-charging performance and cycle performance of the battery cells.

[0073] In some embodiments, the carbonate solvent includes one or more of ethylene carbonate, propylene carbonate, butene carbonate, dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate. The combined use of the above-mentioned carbonate solvents and carboxylic acid ester solvents facilitates lithium-ion migration and improves the fast-charging performance and cycle performance of individual battery cells.

[0074] In some embodiments, the electrolyte further includes an electrolyte lithium salt, the mass content of which is 10% to 18%. When the mass content of the electrolyte lithium salt is within this range, it facilitates the rapid migration of lithium ions, and the electrolyte system is relatively stable and less prone to decomposition, thereby improving the cycle performance and fast-charging performance of the battery cells.

[0075] In some embodiments, the electrolyte lithium salt includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate. When the electrolyte lithium salt includes the above components, it can improve both the cycle performance and fast charging performance of the battery cell.

[0076] In some embodiments, the lithium bis(fluorosulfonyl)imide (LiFSI) content in the electrolyte is 4% to 6% by mass. When the molar concentration of LiFSI is within the above range, the amount of lithium hexafluorophosphate added is relatively low, which can reduce the acid production of lithium hexafluorophosphate, improve the interface stability on the negative electrode side, and help improve the cycle performance of the battery cell.

[0077] In some implementations, the volumetric energy density of the battery cell is between 440 Wh / L and 520 Wh / L.

[0078] Secondly, this application proposes a battery device comprising a plurality of battery cells according to any embodiment of the first aspect of this application.

[0079] Thirdly, this application proposes an electrical device, which includes the battery device according to any embodiment of the second aspect of this application. Attached Figure Description

[0080] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0081] Figure 1 This is a schematic diagram of the structure of a battery cell provided in some embodiments of this application.

[0082] Figure 2 This is an exploded schematic diagram of a battery cell provided in some embodiments of this application.

[0083] Figure 3 This is a schematic diagram of the structure of the electrode assembly of a battery cell provided in some embodiments of this application.

[0084] Figure 4 This is a schematic diagram of the structure of the positive electrode sheet of a battery cell provided in some embodiments of this application.

[0085] Figure 5 This is a schematic diagram of the structure of the positive electrode sheet of a battery cell provided in other embodiments of this application.

[0086] Figure 6 This is a schematic diagram of the structure of the negative electrode sheet of a battery cell provided in some embodiments of this application.

[0087] Figure 7 This is a schematic diagram of the negative electrode sheet of a battery cell provided in other embodiments of this application.

[0088] Figure 8 This is a top view of the electrode assembly of a battery cell provided in some embodiments of this application.

[0089] Figure 9 This is a schematic diagram of the structure of a battery cell provided in some other embodiments of this application.

[0090] Figure 10 This is a schematic diagram of the structure of a battery cell provided in some other embodiments of this application.

[0091] Figure 11 This is a schematic diagram of the structure of a battery cell provided in some other embodiments of this application.

[0092] Figure 12This is a schematic diagram of the structure of a battery module provided in some embodiments of this application.

[0093] Figure 13 This is a schematic diagram of the structure of a battery pack provided in some embodiments of this application.

[0094] Figure 14 This is a schematic diagram of the structure of an electrical device provided in some embodiments of this application.

[0095] The accompanying drawings may not be drawn to scale.

[0096] The annotations in the attached figures are explained as follows:

[0097] 1. Electrical device; 2. Battery pack; 3. Controller; 4. Motor; 5. Housing; 5a. First housing section; 5b. Second housing section; 5c. Storage space; 6. Battery module;

[0098] 7. Battery cell; 10. Electrode assembly;

[0099] 11. Positive electrode sheet; 111. Positive electrode tab; 112. Positive electrode current collector; 113. Positive electrode active material layer;

[0100] 12. Negative electrode sheet; 121. Negative electrode tab; 122. Negative electrode current collector; 123. Negative electrode active material layer;

[0101] 13. Separating membrane;

[0102] 20. Outer shell; 21. Shell; 211. Bottom wall; 212. Side wall;

[0103] 22. End cap; 31. Positive end; 32. Negative end. Detailed Implementation

[0104] The embodiments of this application are disclosed in detail below. However, unnecessary details may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of actually identical structures may be omitted. This is to avoid making the following description unnecessarily lengthy and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0105] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0106] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0107] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0108] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0109] In this application, the term "implementation" means that a specific feature, structure, or characteristic described in connection with an implementation may be included in at least one implementation of this application. The appearance of this phrase in various places in the specification does not necessarily refer to the same implementation, nor is it a separate or alternative implementation mutually exclusive with other implementations.

[0110] In the description of this application, it should be noted that, unless otherwise expressly specified and limited, the terms "installation," "connection," "linking," and "attachment" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal communication between two components. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific circumstances.

[0111] In this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. Additionally, in this application, the character " / " generally indicates that the preceding and following related objects have an "or" relationship.

[0112] In the embodiments of this application, the same reference numerals denote the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments. It should be understood that the thickness, length, width, and other dimensions of various components in the embodiments of this application shown in the drawings, as well as the overall thickness, length, width, and other dimensions of the integrated device, are merely illustrative and should not constitute any limitation on this application.

[0113] In related technologies, in order to improve the energy density of a single battery cell, silicon-based materials are usually introduced into the negative electrode active material layer. Silicon-based materials have a high specific capacity, which is beneficial to significantly improve the energy density of the single battery cell.

[0114] However, with the increase in the amount of silicon-based materials added, the volume expansion of silicon-based materials during the cycle charge and discharge of battery cells has adverse effects. For example, the volume expansion of silicon-based materials can lead to repeated damage to the solid electrolyte interphase (SEI) film on the surface of the negative electrode, requiring continuous film formation and lithium consumption to expose a fresh interface on the negative electrode side, thus reducing the cycle life of the battery cell. Along with the increase in the amount of silicon-based materials added, the amount of binders and other materials used in the negative electrode active material layer needs to be increased simultaneously. Higher binder content can effectively constrain the volume expansion of silicon-based materials; however, the increased use of binders and other materials deteriorates the kinetic performance, hinders fast charging, and may reduce energy density.

[0115] It is difficult for a single battery cell to simultaneously achieve high energy density, excellent cycle performance, and fast charging performance.

[0116] In this application's implementation, the optimization of the negative electrode sheet is mainly used to balance the multiple performance characteristics of the battery cell; specifically:

[0117] First, by limiting the mass content of silicon to an appropriate range, the volumetric energy density of the battery cell can be improved, while reducing the problem of excessive volume expansion caused by the introduction of too much silicon-based material.

[0118] Secondly, an appropriate amount of linear polymer alkali metal salt is added to the negative electrode active material layer. Its adhesiveness effectively binds the particles in the negative electrode active material layer, mitigating the volume expansion of the silicon-based material during charging and discharging. Its linear main chain structure tightly encapsulates the silicon-based material, reducing the adverse effects of volume expansion on the SEI film. By rationally controlling the amount of linear polymer alkali metal salt, while improving the volume expansion of the silicon-based material, its adhesiveness does not significantly affect the kinetic performance of the battery cells, and it essentially does not reduce the capacity of the negative electrode sheet.

[0119] In addition, although silicon-based materials themselves have poor kinetic performance, the alkali metal ions of linear polymer alkali metal salts can provide additional alkali metal ions to the negative electrode active material layer, improve the ion transport rate, and thus improve the kinetic performance of the battery cell and improve fast charging performance.

[0120] In summary, the battery cell can balance high energy density, excellent cycle performance, and fast charging performance.

[0121] battery cell

[0122] In one aspect, this application proposes a battery cell.

[0123] A single battery cell includes an electrode assembly, which includes a positive electrode, a separator, and a negative electrode. The positive electrode includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector. The negative electrode includes a negative current collector and a negative active material layer disposed on at least one side of the negative current collector.

[0124] in,

[0125] The positive electrode active material layer includes lithium phosphate with an olivine structure;

[0126] The negative electrode active material layer includes linear polymer alkali metal salt, silicon-based material and carbon-based material. The mass content of linear polymer alkali metal salt in the negative electrode active material layer is 0.3% to 2%, and the mass content of silicon element in silicon-based material in the negative electrode active material layer is 0.5% to 5%.

[0127] In this embodiment of the application, silicon-based materials are introduced into the negative electrode active material layer, such that the mass content of silicon element is greater than or equal to 0.5%, thereby increasing the specific capacity of the negative electrode active material and improving the capacity of the negative electrode sheet, which in turn can effectively improve the energy density of the battery cell.

[0128] However, with the introduction of silicon-based materials, the volume change of the negative electrode sheet during the cycle charging and discharging of the battery cell is significant, and the SEI film on the negative electrode side is repeatedly damaged, which is detrimental to cycle and fast charging performance. The negative electrode active material layer in the embodiments of this application also includes a linear polymer alkali metal salt. The linear polymer alkali metal salt has adhesiveness, which can bind the particles in the negative electrode active material layer and alleviate the volume expansion of the silicon-based material. Moreover, the main chain structure of the linear polymer without alkali metal salt is linear, which can effectively encapsulate the silicon-based material, alleviate the volume expansion of the silicon-based material, reduce the risk of the silicon-based material damaging the SEI film, and improve the cycle performance and fast charging performance of the battery cell.

[0129] Moreover, the linear polymer alkali metal salt content is not too high, with a mass content of less than or equal to 2%. This improves the volume expansion of silicon-based materials, and the adhesion of the linear polymer alkali metal salt does not cause a deterioration in kinetic performance. This is beneficial for improving the cycle performance and fast charging performance of battery cells.

[0130] Silicon-based materials have poor intrinsic kinetic properties, while the alkali metal ions of linear polymer alkali metal salts can provide alkali metal ions to the negative electrode active material layer, improve the transport rate of alkali metal ions, and help improve the kinetic performance of battery cells and the fast charging performance of battery cells.

[0131] In summary, the battery cell can balance high energy density, excellent cycle performance, and fast charging performance.

[0132] [Positive electrode plate]

[0133] The positive electrode includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector and including a positive active material. For example, the positive current collector has two sides opposite each other in its thickness direction, and the positive active material layer is disposed on either or both sides of the positive current collector.

[0134] In some embodiments, the one-sided surface density of the positive electrode active material layer is 220 mg / 1540.25 mm². 2 Up to 370mg / 1540.25mm 2 For example, 220mg / 1540.25mm 2 230mg / 1540.25mm 2 240mg / 1540.25mm 2 250mg / 1540.25mm 2 260mg / 1540.25mm 2 270mg / 1540.25mm 2 280mg / 1540.25mm 2 290mg / 1540.25mm2 300mg / 1540.25mm 2 310mg / 1540.25mm 2 320mg / 1540.25mm 2 330mg / 1540.25mm 2 350mg / 1540.25mm 2 370mg / 1540.25mm 2 Or a range consisting of any two of the above values.

[0135] When the density of the positive electrode active material layer on one side is within the above range, it is beneficial to balance the energy density and fast charging performance of the battery cell.

[0136] In some embodiments, the compaction density of the positive electrode active material layer is 2.60 g / cm³. 3 Up to 2.85 g / cm 3 For example, the compaction density of the positive electrode active material layer is 2.60 g / cm³. 3 2.65g / cm 3 2.7g / cm 3 2.75g / cm 3 2.8g / cm 3 2.85g / cm 3 Or a range consisting of any two of the above values. Optionally, the compaction density of the positive electrode active material layer is 2.65 g / cm³. 3 Up to 2.80 g / cm 3 .

[0137] The compaction density of the positive electrode active material layer can be the compaction density of the positive electrode active material layer of the battery cell at 0% state of charge (SOC).

[0138] When the compaction density of the positive electrode active material layer is within the aforementioned range, it is beneficial to improve the energy density of the battery cell. Furthermore, because the positive electrode active material layer is densely packed, the contact resistance between particles is low, which further reduces the resistance of the electrode and improves the fast-charging performance of the battery cell. The lower resistance also results in less heat generation within the battery cell and higher electrolyte stability, which is beneficial to improving the cycle performance of the battery cell. Therefore, it is beneficial to balance the energy density, cycle performance, and fast-charging performance of the battery cell.

[0139] The state of a single battery cell is described as follows: 100% State of Charge (SOC) and 0% State of Charge (SOC) of a single battery cell are defined as follows:

[0140] The battery cell is charged at a constant current charging rate of 0.33C to the upper limit of the charging voltage, and then charged at a constant voltage to 0.05C, which corresponds to the 100% SOC state of the battery cell. The battery cell is then discharged at a constant current discharging rate of 0.33C to the discharge cutoff voltage, which corresponds to the 0% SOC state of the battery cell.

[0141] In this embodiment, the single-sided density and compaction density of the positive electrode active material layer can be detected by the following method: The positive electrode sheet is disassembled from a battery cell with 0% SOC. For example, a single-sided coated positive electrode sheet is taken (if it is a double-sided coated electrode sheet, the positive electrode active material layer on one side can be wiped off first), and it is cut into a small circular piece with an area of ​​S1. Its weight is weighed and recorded as M1, and its thickness H1 is measured. Then, the positive electrode active material layer of the weighed positive electrode sheet is wiped off, the weight of the positive electrode current collector is weighed and recorded as M0, and its thickness H0 is measured.

[0142] The density of the positive electrode active material layer on one side = (weight of the positive electrode sheet M1 - weight of the positive electrode current collector M0) / S1, the thickness of the positive electrode active material layer = the thickness of the positive electrode sheet H1 - the thickness of the positive electrode current collector H0, and the compaction density of the positive electrode active material layer = density of the positive electrode active material layer on one side / thickness of the positive electrode active material layer.

[0143] In some embodiments, the compacted density of the olivine-structured lithium phosphate powder at 30000 N is 2.45 g / cm³. 3 Up to 2.75 g / cm 3 For example, 2.45 g / cm³ 3 2.47 g / cm 3 2.48 g / cm 3 2.49 g / cm 3 2.5g / cm 3 2.51g / cm 3 2.55g / cm 3 2.58g / cm 3 2.60g / cm 3 2.65g / cm 3 2.68g / cm 3 2.70 g / cm 3 2.72 g / cm 3 2.75g / cm 3 Or a range consisting of any two of the above values.

[0144] When the compaction density of lithium phosphate powder with an olivine structure is within the aforementioned range at 30,000 N, it can improve the energy density of the battery cell. Furthermore, because the positive electrode active material layer can be more densely packed, the contact resistance between particles is lower, which can further reduce the resistance of the electrode, thereby improving the fast-charging performance of the battery cell. The lower resistance also results in less heat generation within the battery cell and higher electrolyte stability, which is beneficial for improving the cycle performance of the battery cell. Therefore, it is beneficial to balance the energy density, cycle performance, and fast-charging performance of the battery cell.

[0145] In the embodiments of this application, the powder compaction density of the material has a meaning known in the art and can be tested using methods and equipment known in the art, according to the testing standard GB / T 24533-2019. For example, a certain amount of lithium phosphate is taken as a sample and added to a UTM7305 electronic pressure testing machine with a bottom area of ​​1.327 cm². 2 In the mold, the pressure is increased to 3000 kg (equivalent to 30000 N), held for 30 s, then depressurized and held for 10 s. The compaction density of the lithium phosphate powder under a force of 30000 N is then recorded and calculated.

[0146] In some embodiments, the specific surface area of ​​the lithium phosphate with an olivine structure is 9 m². 2 / g to 15m 2 / g, for example 9m 2 / g, 10m 2 / g、11m 2 / g、12m 2 / g、13m 2 / g、14m 2 / g, 15m 2 / g or a range consisting of any two of the above values.

[0147] The specific surface area of ​​lithium phosphates with olivine structure is within the above range, which is conducive to the transport of lithium ions at the interface between lithium phosphate and electrolyte, improves ion conductivity, and enhances the fast charging performance of battery cells.

[0148] In the embodiments of this application, the specific surface area of ​​the material has a meaning known in the art and can be detected using equipment and methods known in the art. For example, it can be detected according to the testing standard GB / T 19587-2017, using lithium phosphate as a sample, and the specific surface area is tested using a Tri-Star 3020 specific surface area and pore size analyzer from Micromeritics, USA.

[0149] In some embodiments, the mass content of the olivine-structured lithium phosphate in the positive electrode active material layer is 96% to 98.5%, for example, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, or any combination of two of the above values.

[0150] When the mass content of lithium phosphate in the positive electrode active material layer meets the above range, it can increase the capacity of the positive electrode active material layer, thereby increasing the energy density of the battery cell.

[0151] In this application embodiment, the mass content of the positive electrode active material has a meaning known in the art and can be detected using equipment and methods known in the art. For example, after discharging the battery cell to 0% state of charge (SOC), the positive electrode sheet is disassembled (if it is a double-sided coated electrode sheet, the positive electrode active material layer on one side can be wiped off first), and the mass content of the positive electrode active material in the positive electrode active material layer is calculated according to the following steps:

[0152] Step 1: Weigh the container and filter membrane together to get the total weight m0;

[0153] Step 2: Combine n positive electrode sheets with a total mass of m2 and a concentration of 25 wt A mixture of concentrated hydrochloric acid (%) was prepared in a container, with a mass ratio of 1:8 between the positive electrode sheet and the concentrated hydrochloric acid. The container was then placed on a heating plate and subjected to a single heating digestion at 180°C for 20 minutes, yielding a single digestion solution of approximately 2.5 mL. The single digestion solution was then vacuum filtered using a filter membrane, and the filter residue was rinsed with 200 mL of water to obtain the rinsed filter residue. The weight of the single positive electrode current collector with the positive electrode active material layer removed was measured as m1.

[0154] Step 3: Mix the filter residue from Step 2 with a concentration of 36... wt % concentrated hydrochloric acid was mixed in a container, with the mass ratio of filter residue to concentrated hydrochloric acid being 1:5. The container was then placed on a heating plate and subjected to secondary heating and digestion at 230°C for 10 minutes to obtain a secondary digestion solution with a volume of approximately 5 mL.

[0155] Step 4: Filter the secondary digestion solution using the filter membrane from Step 2, and rinse the filter residue with 200 mL of water;

[0156] Step 5: Repeat steps 3 and 4 until the filtrate is a colorless and transparent solution, and obtain the product residue. Bake the product residue at 90°C for 10 hours, and then dry it in a desiccator for 1 hour.

[0157] Step Six: Weigh the container, product filter residue, and filter membrane to obtain the total weight m3. Based on the obtained m0, m1, m2, and m3, calculate the content W of the positive electrode active material in the positive electrode sheet according to the formula. t The calculation formula is:

[0158]

[0159] In this embodiment of the application, the lithium phosphate with olivine structure can be phosphate particles or a material obtained by coating and modifying them. For example, the lithium phosphate with olivine structure includes phosphate particles and a positive electrode coating layer. The positive electrode coating layer coats at least part of the surface of the phosphate particles and contains carbon elements.

[0160] Phosphate particles, by coating the surface with a positive electrode coating layer, can improve the conductivity of lithium phosphates with an olivine structure, which is beneficial to the migration rate of lithium ions and improves the fast charging performance of battery cells.

[0161] Examples of phosphate particles include, but are not limited to, one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium nickel phosphate, and lithium cobalt phosphate. These materials exhibit excellent cycle stability and can improve the cycle performance of individual battery cells.

[0162] In some embodiments, lithium phosphates include those with the general formula Li x1 A y1 Me a1 M b1 P 1-c1 X c1 Y z1 The compound, wherein 0.5≤x1≤1.3, 0≤y1≤1.3, 0.5≤x1+y1≤1.3, 0.9≤a1≤1.5, 0≤b1≤0.5, 0.9≤a1+b1≤1.5, 0≤c1≤0.5, 3≤z1≤5, A includes at least one of Na, K and Mg; Me includes at least one of Mn, Fe, Co and Ni; M includes at least one of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La and Ce; X includes at least one of Cl, C and N; Y includes at least one of O and F.

[0163] Phosphate particles exhibit excellent cycle stability, which is beneficial for improving the cycle performance of individual battery cells.

[0164] For example, phosphate particles include one or more of LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4. During the charging and discharging process, active ions such as Li are de-intercalated and consumed in a single battery cell, resulting in different molar contents of Li in different discharged states. In the examples of positive electrode active materials such as LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4, the molar contents of Li represent the initial state of the material, i.e., the state before feeding. When the positive electrode active material is applied to the battery system, the molar contents of Li may change after charge-discharge cycles. In the embodiments of this application, the molar contents of oxygen (O) in the examples of positive electrode active materials such as LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4 are only theoretical values. Lattice oxygen release can cause changes in the molar contents of oxygen (O). In reality, the molar contents of oxygen (O) may fluctuate, and all of the above situations are within the scope of protection of this application.

[0165] In some embodiments, the carbon content in the olivine-structured lithium phosphate is from 0.8% to 2.3% by mass. Exemplarily, the carbon content in the olivine-structured lithium phosphate is 0.8%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, or a range consisting of any two of the above values.

[0166] Carbon primarily exists in the positive electrode coating layer in the form of a carbon coating layer. This loose and porous carbon coating layer is beneficial for increasing the specific surface area of ​​the material, facilitating effective contact between the electrolyte and phosphate particles, and promoting lithium ion transport at the phase interface. Furthermore, when the carbon content is within the aforementioned range, it can significantly improve the conductivity of lithium phosphate with an olivine structure, enhancing both the ionic and electronic conductivity of the lithium phosphate with an olivine structure. Moreover, the amount of carbon added will not be excessive, thus avoiding an excessive reduction in capacity, and can simultaneously improve the rapid charging capability and energy density of the battery cell.

[0167] In some embodiments, the positive electrode coating layer further includes one or more elements of Fe, Ti, Zr, Hf, Ge, and Sn.

[0168] In some embodiments, the positive electrode coating layer includes materials of the general formula Li. 3-d1 Fe 2-d1 M3 d1 (PO m1 ) n1 The compounds wherein 0≤d1≤1, 3≤m1≤5, 2≤n1≤4, and M3 includes one or more of Ti, Zr, Hf, Ge, and Sn.

[0169] Li 3-d1 Fe2-d1 M3 d1 (PO m1 ) n1 The compounds are fast ion conductors with a NASICON structure, such as one or more of lithium iron phosphate (Li2FeTi(PO4)3), lithium zirconium iron phosphate (Li2FeZr(PO4)3), and lithium tin iron phosphate (Li2FeSn(PO4)3).

[0170] Fast ion conductors with a NASICON structure are materials with ultrafast ion conduction capabilities, possessing abundant three-dimensional lithium-ion diffusion and transport channels. They exhibit advantages such as high ion conduction efficiency and strong structural stability during multiple lithium delithiation and lithium intercalation processes. Coating the surface of phosphate particles with fast ion conductors containing a NASICON structure can significantly improve the lithium-ion transport rate during multiple lithium delithiation / intercalation at the positive electrode, enhance the ionic conductivity of the positive electrode active material, improve the fast charging performance of the battery cell, and further increase the specific capacity and energy density of the corresponding battery cell.

[0171] Carbon can exist in the form of allocarbon. Allocarbon and fast ion conductors can be layered, for example, with allocarbon as an independent carbon coating layer and the fast ion conductor as an independent fast ion conductor layer. The carbon coating layer can be applied to the surface of the phosphate particles, with the fast ion conductor layer located on the surface of the carbon coating layer, i.e., on the side of the carbon coating layer away from the phosphate particles. Alternatively, the fast ion conductor layer can be applied to the surface of the phosphate particles, with the carbon coating layer located on the surface of the fast ion conductor layer, i.e., on the side of the fast ion conductor layer away from the phosphate particles. Of course, allocarbon and fast ion conductors can also be layered together.

[0172] Optionally, the carbon coating layer can be formed by carbonizing an organic carbon source (e.g., glucose, polyethylene glycol, etc.) onto the surface of the fast ion conductor layer. The carbon coating layer can partially or completely cover the fast ion conductor layer. The carbon coating layer can significantly improve the electronic conductivity of phosphate particles, compensating for the poor electronic conductivity of phosphate particles and increasing the energy density of the battery cell.

[0173] The positive electrode active material of this application uses lithium phosphate as a substrate, fully leveraging the advantages of lithium phosphate such as low cost, high reliability, and good cycle stability. Simultaneously, it utilizes the positive electrode coating layers (fast ion conductor layer and carbon coating layer) to overcome the drawbacks of poor electronic and ionic conductivity. Battery cells prepared using the positive electrode active material of this application can improve the energy density of battery cells while maintaining excellent cycle performance.

[0174] In this embodiment, the elemental content in the positive electrode active material is defined in a way known in the art and can be detected using equipment and methods known in the art. For example, referring to EPA 6010D-2014, it can be tested by inductively coupled plasma atomic emission spectrometry (ICP-OES, instrument model: Thermo ICAP7400). After discharging the battery cell to 0% state of charge (SOC), the positive electrode sheet is disassembled, cleaned and dried with DMC, and then calcined at high temperature to remove impurities. 0.4g of the positive electrode active material is weighed and 10ml (50% concentration) of aqua regia is added. Then it is placed on a plate at 180°C for 30min. After digestion on the plate, the volume is adjusted to 100mL, and quantitative testing is performed using the standard curve method.

[0175] In some embodiments, the positive electrode active material layer may optionally include a positive electrode conductive agent. This application does not impose particular limitations on the type of positive electrode conductive agent. As an example, the positive electrode conductive agent includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass content of the positive electrode conductive agent is ≤5% based on the mass of the positive electrode active material layer.

[0176] In some embodiments, the positive electrode active material layer may optionally include a positive electrode binder. This application does not impose particular limitations on the type of positive electrode binder. As an example, the positive electrode binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polyacrylic acid, and fluorinated acrylate resins. In some embodiments, the mass content of the positive electrode binder is ≤5% based on the mass of the positive electrode active material layer.

[0177] The positive electrode active material layer is typically formed by coating a positive electrode slurry onto a positive electrode current collector, followed by drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, optional conductive agent, optional binder, and any other components in a solvent and stirring until homogeneous. The solvent can be N-methylpyrrolidone (NMP), but is not limited to this.

[0178] In some embodiments, the positive current collector may be a metal foil or a composite current collector. Examples of metal foils include one or more of aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. The composite current collector may include a polymer substrate and a metal material layer formed on at least one surface of the polymer substrate. Examples of the metal material layer include one or more of aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. Examples of the polymer substrate include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0179] In some embodiments, the thickness of the positive electrode current collector is 10 μm to 15 μm, for example, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or any combination of two of the above values. A thickness of the positive electrode current collector within this range is beneficial for improving current carrying capacity and enhancing the fast-charging performance of the battery cell.

[0180] In the embodiments of this application, the thickness of the positive current collector has a meaning known in the art and can be detected using equipment and methods known in the art, such as performing a tomographic scan on the positive electrode sheet to directly measure the thickness of the positive current collector.

[0181] The positive electrode sheet does not exclude additional functional layers besides the positive electrode active material layer. For example, in some embodiments, the positive electrode sheet of this application further includes a positive electrode conductive layer sandwiched between the positive electrode current collector and the positive electrode active material layer and disposed on the surface of the positive electrode current collector. In other embodiments, the positive electrode sheet of this application further includes a protective layer covering the surface of the positive electrode active material layer.

[0182] In some embodiments, the positive electrode further includes a positive conductive layer located between the positive active material layer and the positive current collector. The positive conductive layer can further improve the conductivity of the positive electrode and reduce the heat generation of the positive electrode, thereby reducing the heat generation of the battery cell.

[0183] In some embodiments, the thickness of the positive electrode conductive layer is from 0.5 μm to 2 μm. For example, the thickness of the positive electrode conductive layer can be 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 1.6 μm, 1.8 μm, 2 μm, or any combination of two of the above values.

[0184] When the thickness of the positive electrode conductive layer is within the above range, the conductivity of the positive electrode sheet can be further improved, the heat generation of the positive electrode sheet can be reduced, thereby reducing the heat generation of the battery cell and improving the fast charging performance and cycle performance of the battery cell at high energy density.

[0185] In the embodiments of this application, the thickness of the positive electrode conductive layer has a meaning known in the art and can be detected using equipment and methods known in the art, such as performing a tomographic scan on the positive electrode sheet to directly measure the thickness of the positive electrode conductive layer.

[0186] In some embodiments, the positive conductive layer includes one or more of a positive conductive agent and a positive binder.

[0187] Optionally, the mass content of the positive electrode conductive agent in the positive electrode conductive layer is 30% to 50%. For example, the mass content of the positive electrode conductive agent is 30%, 35%, 40%, 45%, 50%, or any combination of two of the above values.

[0188] For example, the positive electrode conductive agent in the positive electrode conductive layer includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The positive electrode conductive agent in the positive electrode conductive layer can improve the conductivity of the positive electrode conductive layer, thereby improving the conductivity of the positive electrode sheet and enhancing the fast charging performance of the battery cell.

[0189] Optionally, the positive electrode binder has a mass content of 50% to 70% in the positive electrode conductive layer. For example, 50%, 60%, 65%, 70%, or any combination of two of the above values.

[0190] For example, the positive electrode binder of the positive electrode conductive layer includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, a terpolymer of polyvinylidene fluoride-tetrafluoroethylene-propylene, a terpolymer of polyvinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, a tetrafluoroethylene-hexafluoropropylene copolymer, polyacrylic acid, and fluorinated acrylate resins. The positive electrode binder of the positive electrode conductive layer can improve the adhesion between the positive electrode current collector and the positive electrode active material layer, thereby enhancing the structural stability of the positive electrode sheet.

[0191] [Negative electrode plate]

[0192] The negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one side of the negative current collector and comprising a negative active material. For example, the negative current collector has two sides opposite to each other in its thickness direction, and the negative active material layer is disposed on either or both sides of the negative current collector.

[0193] In some embodiments, the density of the negative electrode active material layer on one side is 80 mg / 1540.25 mm. 2 Up to 160mg / 1540.25mm 2 For example, the one-sided surface density of the negative electrode active material layer is 80 mg / 1540.25 mm². 2

[0194] 100mg / 1540.25mm 2 110mg / 1540.25mm 2 120mg / 1540.25mm 2 122mg / 1540.25mm 2 125mg / 1540.25mm 2 128mg / 1540.25mm 2 130mg / 1540.25mm 2 132mg / 1540.25mm 2 135mg / 1540.25mm 2 137mg / 1540.25mm 2 140mg / 1540.25mm 2 145mg / 1540.25mm 2 150mg / 1540.25mm 2 155mg / 1540.25mm 2 160mg / 1540.25mm 2 Or a range consisting of any two of the above values.

[0195] When the density of the negative electrode active material layer on one side is within the above range, it can improve the energy density and fast charging performance of the battery cell.

[0196] In the embodiments of this application, the one-sided density of the negative electrode active material layer has a meaning known in the art and can be detected using equipment and methods known in the art, such as the one-sided density test method for the positive electrode active material layer.

[0197] In some embodiments, the compaction density of the negative electrode active material layer is 1.25 g / cm³. 3 Up to 1.65 g / cm 3 For example, the compaction density of the negative electrode active material layer is 1.25 g / cm³. 3 1.30g / cm 3 1.35g / cm 3 1.40g / cm 3 1.45g / cm 3 1.50g / cm 3 1.55g / cm 3 1.60g / cm 3 1.65g / cm 3 Or a range consisting of any two of the above values. Optionally, the compaction density of the negative electrode active material layer is 1.35 g / cm³. 3 Up to 1.55 g / cm3 .

[0198] When the compaction density of the negative electrode active material layer is within the above range, it is beneficial to improve the energy density of the battery cell. Furthermore, since the negative electrode active material layer is densely packed, the contact resistance between particles is small, which can further reduce the resistance of the electrode sheet, thereby improving the fast charging performance of the battery cell. The low contact resistance results in less heat generation, making the electrolyte more stable and improving the cycle performance of the battery cell.

[0199] The compaction density of the negative electrode active material layer is the compaction density of the negative electrode active material layer of the battery cell at 0% state of charge (SOC).

[0200] In the embodiments of this application, the compaction density of the negative electrode active material layer has a meaning known in the art and can be detected using equipment and methods known in the art, such as the compaction density test method for the positive electrode active material layer.

[0201] In some embodiments, the mass content of carbon-based materials and silicon-based materials in the negative electrode active material layer is 95% to 98.5%, such as 95%, 96.5%, 97%, 97.5%, 98%, 98.5%, or any range of two of the above values.

[0202] When the mass content of carbon-based and silicon-based materials in the negative electrode active material layer meets the above range, the capacity of the negative electrode active material layer can be increased, thereby improving the energy density of the battery cell.

[0203] In some embodiments, based on the mass of the negative electrode active material layer, the silicon content of the silicon-based material is 0.5% to 5% by mass. Exemplarily, the silicon content of the silicon-based material is 0.5%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, or a range of any two of the above values. Optionally, the silicon content of the silicon-based material is 0.7% to 3.5% by mass.

[0204] When the mass content of silicon in silicon-based materials is within the above range, it can increase the capacity of the negative electrode active material, thereby improving the energy density of the battery cell.

[0205] Optionally, silicon-based materials may include one or more of elemental silicon, silicon-carbon materials, silicon-oxygen materials, silicon-nitrogen materials, and silicon alloys. These materials have high specific capacity, which is beneficial for improving the energy density of individual battery cells.

[0206] Further optionally, the silicon-based material may include one or more of silicon oxide, silicon-carbon, and silicon-nitrogen materials. Even more optionally, the silicon-based material may include silicon-carbon materials. For example, silicon-carbon materials may include silicon carbide. The above materials exhibit relatively good cycle stability during the cycling process of the battery cell, which is beneficial for balancing the improvement of the battery cell's energy density and cycle performance.

[0207] For example, a silicon-carbon material may include a porous carbon framework and silicon disposed within the porous carbon framework, wherein the silicon may be nano-silicon. Nano-silicon may be deposited in the porous carbon framework using methods such as chemical vapor deposition, and the specific process parameters may be those known in the art.

[0208] When silicon-based materials include one or more of silicon oxide, silicon-carbon, and silicon-nitrogen materials, especially when silicon-based materials include silicon-carbon materials, silicon-based materials can further improve the energy density, fast charging performance, and cycle performance of battery cells by improving at least one of the following parameters: mass content of silicon element, volume average particle size, specific surface area, and powder compaction density.

[0209] For example, based on the mass of the silicon-based material, the mass content of silicon element is 40% to 80%, such as 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, or any range of two of the above values.

[0210] For example, the volume average particle size Dv50 of the silicon-based material is from 3.0 μm to 10 μm, such as 3.0 μm, 4.0 μm, 5.0 μm, 5.5 μm, 6.0 μm, 6.5 μm, 7.0 μm, 7.5 μm, 8.0 μm, 8.5 μm, 9.0 μm, 9.5 μm, 10.0 μm or any range of two of the above values.

[0211] In the embodiments of this application, the volume average particle size Dv50 of the material refers to the particle size corresponding to 50% of the volume distribution. It can be detected using equipment and methods known in the art. For example, the material can be used as a sample, and the particle Dv50 can be tested using a Mastersizer 2000E laser particle size analyzer according to the test standard GB / T19077-2024.

[0212] For example, the specific surface area of ​​the silicon-based material is 1m². 2 / g to 3.6m 2 / g, for example, 1m 2 / g, 1.5m 2 / g、2m 2 / g、3m 2 / g, 3.2m 2 / g、3.3m 2 / g, 3.4m2 / g, 3.5m 2 / g, 3.6m 2 / g or a range consisting of any two of the above values.

[0213] The specific surface area of ​​silicon-based materials within the above range is beneficial to the transport of lithium ions at the interface between silicon-based materials and electrolyte, thus improving ion conductivity. In addition, the appropriate active surface of silicon-based materials can reduce interfacial side reactions and improve the cycle performance of battery cells, thereby balancing the fast charging performance and cycle performance of battery cells.

[0214] In the embodiments of this application, the specific surface area of ​​the material has a meaning known in the art and can be detected using equipment and methods known in the art. For example, it can be detected according to the testing standard GB / T 19587-2017, using lithium phosphate as a sample, and the specific surface area is tested using a Tri-Star 3020 specific surface area and pore size analyzer from Micromeritics, USA.

[0215] For example, the compaction density of silicon-based material powder at 25000 N is 0.7 g / cm³. 3 Up to 1.2 g / cm 3 For example, 0.7g / cm 3 0.8g / cm 3 0.9g / cm 3 1.0g / cm 3 1.1g / cm 3 1.2g / cm 3 Or a range consisting of any two of the above values.

[0216] When the powder compaction density of silicon-based materials at 25000N is within the above range, it can improve the energy density of the battery cell. Furthermore, since the negative electrode active material layer can be stacked more tightly, the contact resistance between particles is smaller, which can further reduce the resistance of the electrode sheet and improve the fast charging performance of the battery cell. This is beneficial to balance the energy density and fast charging performance of the battery cell.

[0217] In this application, the powder compaction density of the material has a meaning known in the art and can be tested using methods and equipment known in the art, according to the testing standard GB / T 24533-2019. As an example, a certain amount of material is taken as a sample and added to a UTM7305 electronic pressure testing machine with a base area of ​​1.327 cm². 2 In the mold, the pressure is increased to 2500 kg (equivalent to 25000 N), held for 30 s, then depressurized and held for 10 s. The compaction density of the powder under a force of 25000 N is then recorded and calculated.

[0218] In this application embodiment, the negative electrode active material also includes carbon-based materials, including graphite particles. Graphite particles have high cycle stability and can improve the cycle performance of the battery cell. The positive electrode active material of this application is mainly a lithium phosphate system, and the negative electrode active material is mainly a graphite and silicon-based material system. The combination of the two can improve the energy density of the lithium phosphate system battery cell.

[0219] In some embodiments, the graphite particles include graphite bulk particles and a negative electrode coating layer. The graphite bulk particles include secondary particles, which in turn include multiple primary particles. The negative electrode coating layer coats the surface of the graphite bulk particles and comprises carbon elements. The carbon in the negative electrode coating layer is mainly amorphous carbon, which refers to transitional carbon materials with a very low degree of graphitization and crystallization, exhibiting an approximately amorphous morphology (or lacking a fixed shape and periodic structural regularity). In this application, amorphous carbon refers to the product after carbonization treatment of an organic carbon source.

[0220] The graphite bulk particles include secondary particles. There are multiple migration paths for lithium ions in the graphite bulk particles, and the migration paths in the primary particles are shorter, which can improve the migration rate of lithium ions. The negative electrode coating layer has more end faces and defects, which increases the number of sites where lithium ions can be inserted or extracted, resulting in better conductivity of the negative electrode coating layer. This can reduce the internal resistance of the negative electrode sheet and improve the fast charging performance of the battery cell.

[0221] For example, the graphite bulk particles include one or more of artificial graphite and natural graphite, optionally artificial graphite.

[0222] Optionally, based on the mass of the graphite particles, the carbon content of the negative electrode coating is 2% to 5%, for example, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any combination of two of the above values.

[0223] When the carbon content of the negative electrode coating is within the above range, it can further reduce the internal resistance of the negative electrode sheet, improve the dynamic performance, and improve the fast charging performance of the battery cell. With a smaller internal resistance, the heat generated inside the battery cell is reduced, which is beneficial to improving the stability of the electrolyte and improving the cycle performance of the battery cell.

[0224] In the embodiments of this application, the graphite particles can be prepared using methods known in the art. Taking artificial graphite as an example, the preparation method includes: providing artificial graphite and an organic carbon source, mixing the two, and then carbonizing them to form a negative electrode coating layer on at least a portion of the surface of the artificial graphite particles.

[0225] Optionally, the organic carbon source includes one or more of coal tar pitch, petroleum asphalt, phenolic resin, and coconut shell. Further optionally, the organic carbon source includes petroleum asphalt. Optionally, the softening point of coal tar pitch or petroleum asphalt is below 250°C.

[0226] Optionally, the carbonization temperature is between 700°C and 1800°C. Optionally, the carbonization temperature is between 1000°C and 1300°C. Within a suitable range, the carbonization temperature allows the organic carbon source to be carbonized, forming a negative electrode coating layer containing amorphous carbon on at least a portion of the surface of the artificial graphite.

[0227] Optionally, the carbonization treatment time is 1 hour to 6 hours.

[0228] In some embodiments, the carbon-based material may further include natural graphite. Specifically, the carbon-based material may include graphite particles, or it may include both graphite particles and natural graphite. Optionally, the carbon-based material is graphite particles.

[0229] In some embodiments, the negative electrode active material may include, in addition to the carbon-based and silicon-based materials described above, one or more of tin-based materials and lithium titanate. Tin-based materials may include one or more of elemental tin, tin oxides, and tin alloys.

[0230] The qualitative and quantitative analysis of each substance or element in this application can be performed using suitable equipment and methods known to those skilled in the art. Relevant testing methods can be referenced from domestic and international testing standards and enterprise standards. Furthermore, those skilled in the art can adaptively modify certain testing steps / instrument parameters from the perspective of testing accuracy to obtain more accurate results. One testing method can be used for qualitative or quantitative analysis, or several testing methods can be used in combination for qualitative or quantitative determination.

[0231] For example, the mass content of silicon in the negative electrode active material layer is a well-known concept in the art and can be detected using well-known equipment and methods. For instance, the negative electrode sheet can be immersed in a solvent such as water to separate the negative electrode active material from the negative electrode current collector. The substances in the negative electrode active material layer can be obtained by filtration and used as a test sample. The test sample can be tested using an ICAP7400 inductively coupled plasma atomic emission spectrometer from Thermo Fisher Scientific, USA, in accordance with the GB / T30902-2014 standard, to obtain the mass content of silicon.

[0232] For example, this application can also combine JIS / K0131-1996 General Rules for X-ray Diffraction Analysis to perform X-ray powder diffraction tests and qualitative analysis on negative electrode sheets or negative electrode active materials.

[0233] Artificial graphite and natural graphite can be distinguished by SEM cross-sectional images taken by scanning electron microscope (SEM). Natural graphite has gaps between the sheet-like structures in its SEM cross-section, while artificial graphite has a dense structure with no obvious gaps. Alternatively, they can be distinguished by XRD patterns obtained by X-ray diffraction. Natural graphite has obvious 2H and 3R phases in its XRD pattern, while artificial graphite only has the 2H phase in its XRD pattern.

[0234] In the embodiments of this application, the negative electrode active material layer includes at least one film layer, which can be a single film layer or at least two film layers. The negative electrode active material layer may include two film layers, three film layers, four film layers, or even more film layers.

[0235] In some embodiments, the negative electrode active material layer includes a first negative electrode active material layer and a second negative electrode active material layer. The first negative electrode active material layer is disposed on the surface of the negative electrode current collector, and the second negative electrode active material layer is connected to the side of the first negative electrode active material layer away from the negative electrode current collector. Both the first and second negative electrode active material layers comprise carbon-based materials. Optionally, at least one of the first and second negative electrode active material layers comprises a silicon-based material.

[0236] The negative electrode active material layer comprises at least two film layers. Layered coating is beneficial for improving the fast charging performance and energy density of the battery cell. In particular, when there is a difference between the first and second negative electrode active material layers, it can create a porosity difference in the negative electrode active material layers, reduce the tortuosity of lithium-ion transport, and improve the fast charging performance of the battery cell.

[0237] In some embodiments, at least one of the first negative electrode active material layer and the second negative electrode active material layer comprises a silicon-based material.

[0238] For example, the first negative electrode active material layer includes a silicon-based material. The second negative electrode active material layer can effectively alleviate the volume expansion of the silicon-based material in the first negative electrode active material layer and improve the cycle performance of the battery cell.

[0239] For example, the second negative electrode active material layer includes a silicon-based material, which is beneficial to improving the fast charging performance of the battery cell.

[0240] For example, both the first negative electrode active material layer and the second negative electrode active material layer include silicon-based materials, which is beneficial to improving the energy density of the battery cell.

[0241] In some embodiments, the volume average particle size Dv50 of the negative electrode active material in the first negative electrode active material layer is greater than or equal to the volume average particle size Dv50 of the negative electrode active material in the second negative electrode active material layer. Further optionally, having a larger volume average particle size Dv50 in the first negative electrode active material layer than in the second negative electrode active material layer is beneficial for increasing the compaction density of the negative electrode active material layer. When the negative electrode active material includes a carbon-based material, the volume average particle size Dv50 of the carbon-based material in the first negative electrode active material layer is greater than or equal to the volume average particle size Dv50 of the carbon-based material in the second negative electrode active material layer.

[0242] The difference in particle size between the first and second negative electrode active material layers can improve the fast charging performance of the battery cell. Specifically, the overpotential of the second negative electrode active material layer is usually higher, and the bottleneck of charging is mainly in the second negative electrode active material layer. However, in the embodiments of this application, the particle size of the second negative electrode active material layer is relatively small, which can shorten the solid-phase transport path of lithium ions, improve fast charging performance, improve the problem of lithium deposition on the surface of the negative electrode, and improve cycle performance.

[0243] Optionally, the carbon-based material of the first negative electrode active material layer is particulate, and its volume average particle size Dv50 is 10 μm to 20 μm, for example, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 15 μm, 20 μm or any two of the above values.

[0244] When the volume average particle size Dv50 of the carbon-based material in the first negative electrode active material layer is within the above range, it can shorten the solid-phase transport path of lithium ions and improve fast charging performance. On the other hand, the material is less prone to agglomeration during the preparation process, which can improve the stability of the material and improve cycle performance.

[0245] Optionally, the carbon-based material of the second negative electrode active material layer is particulate, and its volume average particle size Dv50 is 9.5 μm to 14.5 μm, for example, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm or any two of the above values.

[0246] When the volume average particle size Dv50 of the carbon-based material in the second negative electrode active material layer is within the aforementioned range, it can shorten the solid-phase transport path of lithium ions and improve fast charging performance. On the other hand, the material is less prone to agglomeration during preparation, which can improve the stability of the material. Furthermore, the combination of the negative electrode active material in the second negative electrode active material layer and the negative electrode active material in the first negative electrode active material layer within the aforementioned volume average particle size range is beneficial to constructing a gradient porosity difference between the second negative electrode active material layer and the first negative electrode active material layer, reducing the tortuosity of lithium ion transport, enabling lithium ions to quickly gain electrons and be deposited on the negative electrode side, reducing the risk of lithium plating, and improving cycle performance.

[0247] In some embodiments, the thickness ratio of the first negative electrode active material layer to the second negative electrode active material layer is 2:8 to 6:4, for example, 2:8, 3:7, 4:6, 5:5, 6:4, or any range of two of the above values. Optionally, the thickness ratio of the first negative electrode active material layer to the second negative electrode active material layer is 3:7 to 5:5.

[0248] By adjusting the thickness ratio of the first negative electrode active material layer and the second negative electrode active material layer, the gradient porosity difference between the upper and lower layers can be further increased, the lithium-ion transport tortuosity can be reduced, and the fast charging capability of the battery cell can be improved.

[0249] In the embodiments of this application, the thickness of the first negative electrode active material layer and the second negative electrode active material layer are known in the art and can be detected by methods known in the art. For example, the negative electrode sheet is used as a sample, sliced ​​along the thickness direction of the negative electrode active material layer, and then photographed with a scanning electron microscope (SEM) to obtain an SEM cross-sectional image, distinguish the interface between the first negative electrode active material layer and the second negative electrode active material layer, and count the thickness of each film layer.

[0250] In this embodiment, the negative electrode active material layer comprises a linear polymer alkali metal salt. The linear polymer alkali metal salt has a linear structure, comprising a linear main chain and multiple side groups Q branched along the linear main chain. Each side group Q is independently a carboxyl group (-COOH) or an alkali metallized carboxyl group (-COOM, where M is an alkali metal element), and at least a portion of the side groups Q comprises an alkali metallized carboxyl group (-COOM).

[0251] In the embodiments of this application, the mass content of the linear polymer alkali metal salt in the negative electrode active material layer is 0.3% to 2%, for example, 0.3%, 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7%, 1.9%, 2.0%, or any combination of two of the above values.

[0252] When the mass content of linear polymer alkali metal salt is within the above range, it can alleviate the volume expansion of silicon-based materials and provide mobile alkali metal ions for the negative electrode active material layer, thereby improving the cycle performance and fast charging performance of the battery cell; and the amount of linear polymer alkali metal salt added will not be excessive, thus maintaining the high energy density of the battery cell.

[0253] Optionally, the linear polymer alkali metal salt has a mass content of 0.5% to 2% in the negative electrode active material layer, and more preferably 0.7% to 1.3%.

[0254] When the mass content of linear polymer alkali metal salt is within the above range, the encapsulation effect on silicon-based materials is better, which is more conducive to balancing the energy density, cycle performance and fast charging performance of battery cells.

[0255] Optionally, the alkali metal element in the linear polymer alkali metal salt has a mass content of 3% to 7.5%, such as 3%, 4%, 5%, 6%, 7%, 7.5%, or any combination of two of the above values. Exemplarily, the alkali metal element includes one or more elements of lithium, sodium, and potassium, optionally lithium.

[0256] The mass content of alkali metal elements is calculated based on the mass of linear polymer alkali metal salts. When the mass content of alkali metal elements is within the above range, the number of freely moving alkali metal ions in the negative electrode active material layer is relatively large, which can further shorten the distance of alkali metal ions to diffuse to the surface of the negative electrode active material layer, improve the deintercalation rate of alkali metal ions, and improve the fast charging performance of the battery cell.

[0257] Optionally, the number-average molecular weight of the linear polymer alkali metal salt is from 3 kDa to 1000 kDa, for example, 3 kDa, 100 kDa, 200 kDa, 300 kDa, 400 kDa, 500 kDa, 600 kDa, 700 kDa, 800 kDa, 900 kDa, 1000 kDa, or any combination of two of the above values.

[0258] When the number-average molecular weight of linear polymer alkali metal salts is within the above range, the linear polymer alkali metal salts have appropriate viscosity. On the one hand, this can increase the compactness of each particle in the negative electrode active material layer and reduce the contact internal resistance. On the other hand, it can effectively encapsulate silicon-based materials, alleviate the volume expansion of silicon-based materials, and improve the cycle performance and fast charging performance of battery cells.

[0259] Multimolecules of linear polymer alkali metal salts refer to combinations of multiple molecules of linear polymer alkali metal salts, or aggregates of multiple linear polymer alkali metal salts. Because the molecular weight distribution of polymers has a certain degree of polydispersity, they are called multimolecules of linear polymer alkali metal salts.

[0260] The polydispersity index (PDI) of linear polymeric alkali metal salts reflects the molecular weight distribution characteristics of the polymer and is numerically equal to the weight-average molecular weight (M). w ) and number-average molecular weight (M n The ratio of PDI to M w / M n The smaller the PDI, the narrower the molecular weight distribution and the better the uniformity between the molecular weights of different molecules; the larger the PDI, the wider the molecular weight distribution. When PDI = 1, the molecular weight of the polymer is monodisperse, that is, the molecular weight of all molecules in the multi-molecule is numerically equal.

[0261] Optionally, the polydispersity index of the linear polymer alkali metal salt is from 1 to 1.5, for example, 1, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5 or any range of two of the above values.

[0262] When the polydispersity coefficient of linear polymer alkali metal salts is within the above range, the molecular weight distribution of linear polymer alkali metal salts is more concentrated, the performance of linear polymer alkali metal salts is more uniform, and they can more effectively improve the performance of the negative electrode active material layer, which is beneficial to improving the cycle performance and fast charging performance of battery cells.

[0263] Optionally, the linear polymer alkali metal salt includes one or more of polyacrylate alkali metal salts and polymethacrylate alkali metal salts. Optionally, the linear polymer alkali metal salt includes one or more of linear polymer lithium salts, linear polymer sodium salts, and linear polymer potassium salts. Optionally, the linear polymer alkali metal salt includes a linear polymer lithium salt.

[0264] For example, the alkali metal salt of polyacrylate includes one or more of lithium polyacrylate, sodium polyacrylate, and potassium polyacrylate. Optionally, the alkali metal salt of polyacrylate includes lithium polyacrylate.

[0265] For example, the alkali metal salt of polymethacrylate includes one or more of lithium polymethacrylate, sodium polymethacrylate, and potassium polymethacrylate. Optionally, the alkali metal salt of polymethacrylate includes lithium polymethacrylate.

[0266] In the embodiments of this application, the chemical structural characteristics of linear polymer alkali metal salts can be characterized and analyzed using test methods including, but not limited to, the following: electrochemical analysis methods, 1 1H NMR nuclear magnetic spectroscopy, 13 Methods include C11 NMR, Fourier transform infrared (FT-IR) spectroscopy, Raman spectroscopy, and inductively coupled plasma atomic emission spectrometry (ICP).

[0267] In the embodiments of this application, molecular weight characteristics such as molecular weight and molecular weight distribution of linear polymer alkali metal salts can be characterized and analyzed using methods including but not limited to: gel permeation chromatography (GPC), high-performance liquid chromatography (HPLC), and mass spectrometry. Furthermore, specific values ​​related to number-average molecular weight, weight-average molecular weight, and PDI can be obtained through GPC testing and analysis.

[0268] Unless otherwise specified in this application, the mass content of alkali metal elements in linear polymer alkali metal salts can be tested using the following method (which can be denoted as F). M Or n%, where n is a suitable positive number and % represents the mass content): Take a certain mass m0 of linear polymer alkali metal salt as a sample, and use inductively coupled plasma atomic emission spectrometry (ICP) to test the mass m1 of the alkali metal element (such as lithium). Then, the mass content of the alkali metal element in the linear polymer alkali metal salt (F) is... M ) = m1 / m0 × 100%;

[0269] The sample can be prepared by the following method:

[0270] At 25°C, the freshly prepared battery cell was charged to 3.8V at a charging rate of 0.5C, then charged at a constant voltage of 3.8V to 0.05C, allowed to stand for 10 minutes, and then discharged to 2.0V at a discharging rate of 0.33C, allowed to stand for 10 minutes, and then discharged to 2.0V at a discharging rate of 0.01C. The battery cell was disassembled, the negative electrode was removed, and the negative electrode was immersed in dimethyl carbonate (DMC) solvent for 12 hours. After removal, the negative electrode was rinsed twice with DMC. In this embodiment, the freshly prepared battery cell refers to a battery cell with fewer than 10 cycles after coating.

[0271] The negative electrode sheet was dried in a vacuum drying oven at 80°C for 12 hours. The negative electrode active material layer was scraped off and used as a sample. The content of alkali metal elements was determined by inductively coupled plasma atomic emission spectrometry (ICP).

[0272] In some embodiments, the negative electrode active material layer further includes a negative electrode binder, which includes one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, waterborne acrylic resins (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, based on the total weight of the negative electrode active material layer, the mass content of the negative electrode binder is from 0.5% to 3.5%, for example, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, or any combination of two of the above values. Optionally, the mass content of the negative electrode binder is from 0.5% to 2%.

[0273] When the mass content of the negative electrode binder is within the above range, it can improve the bonding force between the negative electrode active material layer and the negative electrode current collector, reduce the risk of layer delamination during cycling, and improve the cycle performance of the battery cell.

[0274] In some embodiments, when the negative electrode active material layer is a single-layer film, the negative electrode active material layer further includes a linear polymer alkali metal salt. Optionally, the negative electrode active material layer may further include a negative electrode binder.

[0275] For example, the negative electrode binder of the negative electrode active material layer includes one or more of styrene-butadiene rubber, water-soluble unsaturated resin, water-based acrylic resin, polyvinyl alcohol, sodium alginate and carboxymethyl chitosan.

[0276] In other embodiments, where the negative electrode active material layer comprises at least two film layers, the first negative electrode active material layer may optionally further comprise a linear polymer alkali metal salt, and the second negative electrode active material layer may further comprise a linear polymer alkali metal salt.

[0277] Optionally, the mass content of the linear polymer alkali metal salt in the first negative electrode active material layer is greater than or equal to the mass content of the linear polymer alkali metal salt in the second negative electrode active material layer.

[0278] Alternatively, the mass content of the linear polymer alkali metal salt in the first negative electrode active material layer is equal to the mass content of the linear polymer alkali metal salt in the second negative electrode active material layer.

[0279] The linear polymer alkali metal salt has a relatively high mass content in the first negative electrode active material layer. The linear polymer alkali metal salt provides the first negative electrode active material layer with a relatively larger number of freely mobile alkali metal ions, such as lithium ions, which can further improve the fast charging performance of the battery cell.

[0280] For example, the mass content of the linear polymer alkali metal salt relative to the first negative electrode active material layer is from 0.3% to 2.5%, such as 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2.0%, 2.5%, or any combination of two of the above values. The lithium element in the linear polymer alkali metal salt can exist in ionic form, which can increase the number of freely moving alkali metal ions, such as lithium ions, in the negative electrode active material layer, shorten the distance that lithium ions diffuse to the surface of the negative electrode active material layer, improve the lithium ion insertion / extraction rate, and enhance the fast charging performance of the battery cell.

[0281] For example, the mass content of the linear polymer alkali metal salt relative to the second negative electrode active material layer is 0.2% to 1.5%, such as 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, or any combination of the above values. The lithium element in the linear polymer alkali metal salt can exist in ionic form, which can increase the number of freely moving alkali metal ions, such as lithium ions, in the negative electrode active material layer, shorten the distance that lithium ions diffuse to the surface of the negative electrode active material layer, improve the lithium ion insertion / extraction rate, and enhance the fast charging performance of the battery cell.

[0282] The linear polymer alkali metal salt of the first negative electrode active material layer and the linear polymer alkali metal salt of the first negative electrode active material layer can be made of the same material or different materials.

[0283] In some embodiments, the first negative electrode active material layer further includes a negative electrode binder, and the second negative electrode active material layer further includes a negative electrode binder.

[0284] For example, the negative electrode binder of the second negative electrode active material layer includes one or more of styrene-butadiene rubber, water-soluble unsaturated resin, water-based acrylic resin, polyvinyl alcohol, sodium alginate and carboxymethyl chitosan.

[0285] For example, the negative electrode binder of the second negative electrode active material layer includes one or more of styrene-butadiene rubber, water-soluble unsaturated resin, water-based acrylic resin, polyvinyl alcohol, sodium alginate and carboxymethyl chitosan.

[0286] In some embodiments, the linear polymer alkali metal salt of the first negative electrode active material layer has a mass content of A1% in the first negative electrode active material layer; the negative electrode binder of the first negative electrode active material layer has a mass content of B1% in the first negative electrode active material layer.

[0287] The linear polymer alkali metal salt in the second negative electrode active material layer has a mass content of A2%; the negative electrode binder in the second negative electrode active material layer has a mass content of B2%.

[0288] Where A1% + B1% ≥ A2% + B2%.

[0289] The high total mass content of the linear polymer alkali metal salt and negative electrode binder in the first negative electrode active material layer results in a strong bond between the negative electrode active material layer and the negative electrode current collector. During the cycle of the battery cell, the negative electrode sheet exhibits excellent cycle stability, which is beneficial for improving the cycle performance of the battery cell.

[0290] For example, A1%+B1% ranges from 0.5% to 3.5%. A1%+B1% represents the total mass content of the linear polymer alkali metal salt and the negative electrode binder in the first negative electrode active material layer, such as 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 3.0%, 3.5%, or a range of any two of the above values. When the negative electrode active material layer meets the above conditions, it is beneficial to improve both the cycle performance and energy density of the battery cell.

[0291] For example, A2%+B2% is 0.5% to 2.5%. A2%+B2% represents the total mass content of the linear polymer alkali metal salt and the negative electrode binder in the second negative electrode active material layer, such as 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2%, 2.5%, or a range of any two of the above values. When the negative electrode active material layer meets the above conditions, it is beneficial to improve both the cycle performance and energy density of the battery cell.

[0292] In some embodiments, the negative electrode active material layer also includes carbon nanotubes. On the one hand, carbon nanotubes can improve the conductivity of the negative electrode sheet. On the other hand, carbon nanotubes have a linear structure and can be wrapped around the surface of silicon-based materials, alleviating the volume expansion of silicon-based materials and improving the fast charging performance and cycle performance of battery cells.

[0293] Optionally, the mass content of carbon nanotubes in the negative electrode active material layer is 0.01% to 1%, for example, 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1%, or any range of two of the above values.

[0294] When the mass content of carbon nanotubes is within the above range, it can further improve the fast charging performance and cycle performance of battery cells.

[0295] Optionally, the length of the carbon nanotubes is from 1 μm to 5 μm, such as 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm or any combination of two of the above values.

[0296] Carbon nanotubes can generally be considered as two-dimensional carbon materials rolled up. When the number of layers formed by the rolling is single, it is a single-walled carbon nanotube; when the rolling is multi-layered, it is a multi-walled carbon nanotube. The diameter of a carbon nanotube is the outer diameter of the carbon nanotube along a cross-section perpendicular to its own central axis.

[0297] Optionally, carbon nanotubes include one or more types of single-walled carbon nanotubes and multi-walled carbon nanotubes.

[0298] In some embodiments, the negative electrode active material layer may optionally include a negative electrode conductive agent. This application does not impose particular limitations on the type of negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass content of the negative electrode conductive agent is ≤5% based on the total weight of the negative electrode active material layer.

[0299] In some embodiments, the negative electrode active material layer may optionally include other additives. As examples, other additives may include thickeners, dispersants, etc., such as sodium carboxymethyl cellulose (CMC-Na), PTC thermistor materials, etc. In some embodiments, the mass content of other additives is ≤2% based on the total weight of the negative electrode active material layer.

[0300] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. Examples of metal foils include one or more of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. The composite current collector may include a polymer substrate and a metal material layer formed on at least one surface of the polymer substrate. As an example, the metal material layer may include one or more of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymer substrate may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0301] The negative electrode active material layer is typically formed by coating a negative electrode slurry onto a negative electrode current collector, followed by drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional additives in a solvent and stirring until homogeneous. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited to these.

[0302] In some embodiments, the porosity of the negative electrode active material layer is 25% to 40%, for example, 25%, 30%, 35%, 40%, or any combination of two of the above values.

[0303] When the porosity of the negative electrode active material layer is within the above range, it can improve the wetting rate of the electrolyte in the negative electrode active material layer, increase the liquid phase diffusion rate, and help improve the fast charging capability of the battery cell.

[0304] In the embodiments of this application, porosity refers to the percentage of the pore volume within the negative electrode active material layer to the total volume of the negative electrode active material layer. Porosity can be tested according to the standard GB / T36363-2018 "Polyolefin Separators for Battery Cells".

[0305] In some embodiments, the thickness of the negative electrode current collector is 4 μm to 6 μm, for example, 4 μm, 5 μm, 6 μm, or any combination of two of the above values. When the thickness of the negative electrode current collector is within the above range, the thickness of the negative electrode current collector is relatively thin, which is beneficial to improving the volumetric energy density of the battery cell.

[0306] The testing method for the thickness of the negative electrode current collector is the same as that for the thickness of the positive electrode current collector, and will not be repeated here.

[0307] In this embodiment, the negative electrode current collector includes a metal current collector or a composite current collector.

[0308] For example, when the negative electrode current collector includes a metal current collector, the metal current collector includes copper or a copper-based alloy. For example, copper-based alloys include copper-nickel alloys, copper-titanium alloys, or copper-silver alloys.

[0309] For example, when the negative electrode current collector includes a composite current collector, the composite current collector includes a support layer and a conductive layer disposed on at least one side of the support layer. The support layer includes one or more of a polymer material and a polymer-based composite material, and the conductive layer includes copper or a copper-based alloy.

[0310] For example, polymeric materials include one or more of the following: polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polypropylene, polypropylene, acrylonitrile-butadiene-styrene copolymer, polyvinyl alcohol, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, sodium polystyrene sulfonate, polyacetylene, silicone rubber, polyoxymethylene, polyphenylene ether, polyphenylene sulfide, polyethylene glycol, sulfur polynitrides, polyphenylene, polypyrrole, polyaniline, polythiophene, polypyridine, cellulose, starch, protein, epoxy resin, and phenolic resin.

[0311] For example, polymer-based composite materials include polymer materials and metallic materials, and the metallic materials include one or more of magnesium, calcium, strontium, lead, zinc, tin, antimony, bismuth, silver and ruthenium.

[0312] The negative electrode sheet does not exclude additional functional layers besides the negative electrode active material layer. For example, in some embodiments, the negative electrode sheet of this application further includes a negative electrode conductive layer sandwiched between the negative electrode current collector and the negative electrode active material layer and disposed on the surface of the negative electrode current collector. In other embodiments, the negative electrode sheet of this application further includes a protective layer covering the surface of the negative electrode active material layer.

[0313] In some embodiments, the negative electrode sheet further includes a negative electrode conductive layer, which is located between the negative electrode active material layer and the negative electrode current collector. The negative electrode conductive layer can further improve the conductivity of the negative electrode sheet, reduce the heat generation of the negative electrode sheet, thereby reducing the heat generation of the battery cell and improving the fast charging performance and cycle performance of the battery cell.

[0314] In some embodiments, the thickness of the negative electrode conductive layer is from 0.5 μm to 2 μm. Exemplarily, the thickness of the negative electrode conductive layer can be 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 1.6 μm, 1.8 μm, 2 μm, or any combination of two of these values. While the negative electrode conductive layer can improve the fast-charging performance of a single battery cell, it also encroaches on the space of the active material, leading to a reduction in electrode capacity. Setting the thickness of the negative electrode conductive layer within an appropriate range can balance the energy density and fast-charging performance of the single battery cell.

[0315] In the embodiments of this application, the thickness of the negative electrode conductive layer has a meaning known in the art and can be detected using equipment and methods known in the art, such as performing a tomographic scan on the negative electrode sheet to directly measure the thickness of the negative electrode conductive layer.

[0316] In some embodiments, the negative electrode conductive layer includes one or more of a negative electrode conductive agent and a negative electrode binder. The negative electrode conductive agent in the negative electrode conductive layer can improve the conductivity of the negative electrode conductive layer, thereby improving the conductivity of the negative electrode sheet and reducing the heat generation of the battery cell. The negative electrode binder in the negative electrode conductive layer can improve the bonding performance between the negative electrode current collector and the negative electrode active material layer, thereby improving the structural stability of the negative electrode sheet.

[0317] In some embodiments, the negative electrode conductive layer may optionally include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose, PTC thermistor materials, etc.

[0318] Optionally, the negative electrode conductive agent in the negative electrode conductive layer has a mass content of 20% to 40%. For example, the mass content of the negative electrode conductive agent is 20%, 25%, 30%, 35%, 40%, or any combination of two of the above values.

[0319] For example, the negative electrode conductive agent of the negative electrode conductive layer includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0320] Optionally, the negative electrode binder in the negative electrode conductive layer has a mass content of 60% to 80% in the negative electrode conductive layer. For example, 60%, 65%, 70%, 75%, 80%, or any combination of two of the above values.

[0321] For example, the negative electrode binder of the negative electrode conductive layer includes one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin, polyvinyl alcohol, sodium alginate, and carboxymethyl chitosan.

[0322] [Isolation membrane]

[0323] In this embodiment, the separator is disposed between the positive electrode and the negative electrode to isolate the positive electrode and the negative electrode.

[0324] In this embodiment, the separator membrane includes a porous base membrane.

[0325] In some embodiments, the base film includes one or more of glass fiber, nonwoven fabric, and polyolefin. The base film can be a single-layer film or a multi-layer composite film, without particular limitation. When the base film is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0326] Alternatively, the polyolefin includes one or more of polyethylene, polypropylene, and polyvinylidene fluoride.

[0327] In some embodiments, the porosity of the separator is 20% to 70%, optionally 35% to 60%. Exemplarily, the porosity of the separator is 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, or any range of two of the above values.

[0328] When the porosity of the separator in the embodiments of this application is within the above-mentioned range, it can improve the migration ability of lithium ions in the separator, further reduce the internal resistance of the battery cell, thereby reducing heat generation, and can balance the fast charging performance and cycle performance of the battery cell.

[0329] In this embodiment, porosity refers to the percentage of the pore volume of the separator to the total volume of the separator. Porosity can be tested according to the standard GB / T 36363-2018 "Polyolefin Separators for Battery Cells". It should be noted that the actual testing process may differ slightly from the standard due to differences in testing instruments, testing errors, and to minimize the impact on porosity testing, in order to obtain more accurate test values.

[0330] In some embodiments, the thickness of the base film is 4 μm to 7 μm. Exemplarily, the thickness of the base film is 4 μm, 5 μm, 6 μm, 6.5 μm, 7 μm, or any range of two of the above values.

[0331] When the thickness of the base film is within the above range, the migration path of lithium ions in the separator is shorter, which can further reduce the internal resistance of the battery cell and make the separator occupy less space overall, thus improving both the fast charging performance and energy density of the battery cell.

[0332] In the embodiments of this application, the thickness of the membrane layer has a meaning known in the art. It can be detected using a meaning and equipment known in the art. For example, a newly prepared separator can be taken as a sample, or a battery cell that has been completely discharged (discharged to the lower limit cutoff voltage so that the charge state of the battery cell is about 0% SOC) can be disassembled in reverse, the separator can be obtained from the battery cell, and the separator can be dried and used as a sample. The separator can be cut with an ion beam cutter to form a cross section. Subsequently, the thickness of the separator and its various layers can be measured using a scanning electron microscope.

[0333] In some implementations, the separator can be a base membrane.

[0334] In some embodiments, the separator further includes a first functional layer disposed on at least one side of the base film. The first functional layer may include inorganic particles to improve the heat resistance of the separator. Optionally, the first functional layer is disposed on both sides of the base film. For example, the first functional layer is disposed on at least one side of the base film along the thickness direction of the separator itself.

[0335] For example, the inorganic particles include one or more of silicon oxide, aluminum oxide, boehmite, barium sulfate, calcium oxide, titanium oxide, zinc oxide, magnesium oxide, zirconium oxide, and tin oxide. These inorganic particles can improve the heat resistance of the first functional layer.

[0336] For example, the average particle size of the inorganic particles is from 5 nm to 100 nm, optionally from 10 nm to 100 nm, or optionally from 5 nm to 20 nm. For instance, the average particle size of the inorganic particles is 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, or any combination of two of the above values. When the average particle size of the inorganic particles is within the above range, it is beneficial to improve the heat resistance and compressive modulus of the separator.

[0337] In the embodiments of this application, the average particle size of inorganic particles has a meaning known in the art and can be detected using equipment and methods known in the art. For example, after obtaining the separator membrane and drying it as a sample, the separator membrane is cut with an ion beam cutter to form a cross-section. Subsequently, the particle size of inorganic particles in the separator membrane is measured using a scanning electron microscope. The particle size of multiple inorganic particles, such as 50, is measured, and their average value is calculated as the average particle size.

[0338] Optionally, the first functional layer may further include an adhesive. The adhesive may include one or more of fluorinated adhesives or polyacrylic adhesives. Specifically, the fluorinated adhesive includes polyvinylidene fluoride, polytetrafluoroethylene, a terpolymer of vinylidene fluoride-tetrafluoroethylene-propylene, a terpolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, and a tetrafluoroethylene-hexafluoropropylene copolymer. The polyacrylic adhesive includes one or more of polyacrylic acid and fluorinated acrylate resins.

[0339] In some embodiments, the separator further includes a second functional layer disposed on at least one side of the base film. The second functional layer may include an adhesive, which can improve the bonding ability of adjacent film layers in the separator and reduce the risk of short circuit between the negative and positive electrodes, thereby improving the reliability of the battery cell. For example, the second functional layer is disposed on at least one side of the base film along the thickness direction of the separator itself.

[0340] Optionally, the second functional layer is disposed on both sides of the base film. For example, the adhesive may include one or more of fluorinated adhesives or polyacrylic adhesives. Specifically, fluorinated adhesives include polyvinylidene fluoride, polytetrafluoroethylene, ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, and tetrafluoroethylene-hexafluoropropylene copolymer. Polyacrylic adhesives include one or more of polyacrylic acid and fluorinated acrylate resins.

[0341] Alternatively, the second functional layer is located on the side of the first functional layer away from the base film.

[0342] For example, the separator includes a first functional layer and a second functional layer. The first functional layer is located on both sides of the base membrane, and the second functional layer is located on one side of the base membrane, on the side of the first functional layer away from the base membrane. In this case, the second functional layer can be disposed close to the negative electrode.

[0343] For example, the separator includes a first functional layer and a second functional layer, the first functional layer being located on both sides of the base membrane, and the second functional layer being located on both sides of the base membrane, and on the side of the first functional layer away from the base membrane.

[0344] Electrolyte

[0345] In this embodiment of the application, the battery cell also includes an electrolyte.

[0346] During the charging and discharging process of a single battery cell, active ions such as lithium ions are inserted and extracted back and forth between the positive and negative electrode plates, and the electrolyte plays the role of conducting active ions between the positive and negative electrode plates.

[0347] In some embodiments, the electrolyte has a conductivity of 13 mS / cm to 18 mS / cm at room temperature, for example, 13 mS / cm, 13.5 mS / cm, 14 mS / cm, 14.5 mS / cm, 15 mS / cm, 15.5 mS / cm, 16 mS / cm, 16.5 mS / cm, 17 mS / cm, 17.5 mS / cm, 18 mS / cm, or any range of two of the above values. Optionally, the electrolyte has a conductivity of 13.5 mS / cm to 16 mS / cm at room temperature.

[0348] When the conductivity of the electrolyte at room temperature is within the above range, the migration rate of lithium ions in the electrolyte is relatively high, which can further reduce the internal resistance of the battery cell, thereby reducing heat generation and improving the fast charging performance and cycle performance of the battery cell.

[0349] In the embodiments of this application, the conductivity of the electrolyte at room temperature is the ionic conductivity, which can be detected using equipment and methods known in the art, such as by referring to industry standard HG-T 4067-2015.

[0350] In the embodiments of this application, room temperature refers to the ambient temperature, which can be from 15°C to 30°C. For example, when conducting parameter testing in this application, the sample can be placed in an environment of 25°C for testing.

[0351] In some embodiments, the electrolyte contains carbonate additives at a mass content of 0.5% to 10%, and the carbonate additives include at least one of vinylene carbonate and ethylene carbonate derivatives, wherein the ethylene carbonate derivatives include compounds represented by Formula A.

[0352]

[0353] In Formula A, Q1, Q2, Q3 and Q4 each independently include any one of a hydrogen atom, a halogen atom, a C1 to C5 alkyl group, or a C1 to C5 haloalkyl group, and at least one of Q1, Q2, Q3 and Q4 includes a halogen atom, a C1 to C5 alkyl group, or a C1 to C5 haloalkyl group.

[0354] Carbonate additives can optimize the composition of the SEI film on the negative electrode side, alleviate the volume expansion of silicon-based materials, and improve the cycle performance and fast charging performance of battery cells.

[0355] For example, one of Q1, Q2, Q3, and Q4 includes a halogen atom, a C1 to C5 alkyl group, or a C1 to C5 haloalkyl group, and the remainder are hydrogen atoms.

[0356] For example, at least two of Q1, Q2, Q3, and Q4 include a halogen atom, a C1 to C5 alkyl group, or a C1 to C5 haloalkyl group.

[0357] For example, at least three of Q1, Q2, Q3, and Q4 include halogen atoms, C1 to C5 alkyl groups, or C1 to C5 haloalkyl groups.

[0358] For example, Q1, Q2, Q3, and Q4 each independently include a halogen atom, a C1 to C5 alkyl group, or a C1 to C5 haloalkyl group.

[0359] Optionally, at least one of Q1, Q2, Q3, and Q4 includes a halogen atom or a C1 to C5 haloalkyl group. The halogen atom includes a fluorine atom, a bromine atom, or a chlorine atom, and may be a fluorine atom. The C1 to C5 haloalkyl group includes a C1 to C5 fluoroalkyl group, a C1 to C5 bromoalkyl group, or a C1 to C5 chloroalkyl group, and may be a fluorine atom. For example, the C1 to C5 fluoroalkyl group includes fluoromethyl, fluoroethyl, fluoropropyl, fluorobutyl, or fluoropentyl.

[0360] When ethylene carbonate derivatives include fluorine atoms, they can form a film rich in F and Li on the negative electrode side. This film can protect the negative electrode active material while reducing the impedance of the film, thus more effectively improving the energy density, fast charging performance, and cycle performance of the battery cell.

[0361] For example, ethylene carbonate derivatives include one or more of fluoroethylene carbonate, difluoroethylene carbonate, and trifluoromethylethylene carbonate.

[0362] For example, carbonate additives include one or more of vinylene carbonate (VC) and fluoroethylene carbonate (FEC).

[0363] For example, the carbonate additive in the electrolyte is 0.5% to 10% by mass, such as 0.5%, 1.0%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any combination of two of the above values.

[0364] Adding certain substances, such as additives, to the electrolyte can have a significant impact. Because these additives participate in film formation on the surface of active materials, their content in the electrolyte of a battery cell is related to its freshness, formation status, battery life cycle, and storage condition. Therefore, the additive content in a freshly prepared electrolyte may differ from that in an electrolyte obtained from reverse-engineered batteries. However, those skilled in the art can determine the approximate range of the relevant substance content in the fresh electrolyte based on the battery cell's performance level (e.g., cycle count) and residual content. Similarly, those skilled in the art can determine the approximate range of the additive content in a non-freshly prepared (i.e., reverse-engineered) electrolyte based on the additive content in a freshly prepared electrolyte, considering the battery cell's performance requirements and storage environment.

[0365] Therefore, the additive content mentioned in the technical solution of this application can be the content of additives actively added to fresh electrolyte, or the content of residual additives detected by reverse detection based on the actual battery state.

[0366] For example, the carbonate additive in the electrolyte is 2% to 10% by mass, such as 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any combination of two of the above values.

[0367] Carbonate additives can be actively added to fresh electrolyte. When their mass content is within the above range, they can form an excellent SEI film on the negative electrode side, which can improve the interface stability on the negative electrode side. Moreover, the SEI film has low impedance, thereby improving the cycle performance and fast charging performance of the battery cell.

[0368] For example, the mass content of carbonate additives in the electrolyte is 0.5% to 8%, which can be understood as obtaining the carbonate additive content in the electrolyte of the battery cell after formation.

[0369] For example, the mass content of carbonate additives in the electrolyte is 1% to 6%, which can be understood as the carbonate additive content of freshly prepared electrolyte. When the mass content of carbonate additives is within the above range, it can more effectively balance the cycle performance and fast charging performance of battery cells.

[0370] In some embodiments, the electrolyte includes a sulfur-containing additive, which includes one or more of vinyl sulfate DTD, 2-vinyl disulfate DTD, butylene sulfite BS, 1,3-propanesulfonate lactone PS, vinyl sulfite ES, and methylene disulfonate MMDS.

[0371] Optionally, the sulfur-containing additive in the electrolyte has a mass content of 0.3% to 2%, for example, 0.3%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, or any combination of two of the above values. The sulfur-containing additive can form a dense SEI film on the negative electrode side, effectively mitigating the risk of side reactions between the electrolyte and the negative electrode active material, reducing gas production, and improving the cycle performance of the battery cell.

[0372] In some embodiments, the electrolyte includes lithium salt additives, including one or more of lithium difluorophosphate (LiPO2F2), lithium difluorooxalate borate (LiDFOB), lithium tetrafluoroborate (LiBF4), and lithium dioxalate borate (LiBOB).

[0373] Optionally, the lithium salt additive in the electrolyte has a mass content of 0.1% to 3%, for example, 0.3%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.5%, 3%, or any combination of two of the above values. The lithium salt additive participates in film formation, optimizing the SEI film composition. It can also contribute to the formation of an inorganic-rich SEI film, which enhances the high-temperature and high-voltage stability of the SEI film and improves the cycle performance of the battery cells.

[0374] Electrolytes consist of organic solvents and electrolyte salts. The types of organic solvents and electrolyte salts are not specifically limited and can be selected according to actual needs.

[0375] In some embodiments, the organic solvent includes carboxylic acid ester solvents, optionally including linear carboxylic acid ester solvents. Further optionally, the carboxylic acid ester solvent has a mass content of 10% to 60% in the electrolyte, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, or any range of two of the above values. Optionally, the linear carboxylic acid ester solvent has a mass content of 30% to 60% in the electrolyte.

[0376] When the mass content of carboxylic acid ester solvents is within the above range, it is beneficial to the migration of lithium ions and can improve the fast charging performance and cycle performance of battery cells.

[0377] In some embodiments, the carboxylic acid ester solvent includes compounds represented by Formula I.

[0378]

[0379] In formula I,

[0380] R1 includes a hydrogen atom, a C1 to C5 alkyl group, or a C1 to C5 haloalkyl group.

[0381] R2 includes C1 to C5 alkyl or C1 to C5 haloalkyl.

[0382] The aforementioned carboxylic acid ester solvents facilitate lithium ion migration and improve the fast charging capability of individual battery cells.

[0383] Optionally, R1 includes a hydrogen atom, a C1 to C3 alkyl group, or a C1 to C3 haloalkyl group. More optionally, R1 includes a hydrogen atom, a C1 to C2 alkyl group, or a C1 to C2 haloalkyl group.

[0384] Optionally, R2 comprises a C1 to C3 alkyl group or a C1 to C3 haloalkyl group. More optionally, R2 comprises a C1 to C2 alkyl group or a C1 to C2 haloalkyl group.

[0385] In the above embodiments, the halogenated alkyl group includes one or more of fluoroalkyl, chloroalkyl, bromoalkyl and iodoalkyl groups, and optionally, the halogenated alkyl group includes fluoroalkyl.

[0386] For example, carboxylic acid ester solvents include one or more of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, methyl butyrate, and ethyl butyrate.

[0387] In some embodiments, the organic solvent further includes a carbonate solvent, wherein the carbonate solvent comprises 20% to 70% by mass in the organic solvent, for example, 20%, 25%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 40%, 45%, 48%, 50%, 55%, 60%, 65%, 70%, or any combination of two of the above values. The carbonate solvent at the above mass content can further improve the conductivity of the electrolyte at room temperature, which is beneficial for lithium-ion migration and can improve the fast-charging performance and cycle performance of the battery cells.

[0388] Optionally, the carbonate solvent includes one or more of ethylene carbonate, propylene carbonate, butene carbonate, dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate. The combined use of the above-mentioned carbonate solvents and carboxylic acid ester solvents is beneficial for lithium-ion migration, thereby improving the fast-charging performance and cycle performance of individual battery cells.

[0389] In some embodiments, the electrolyte includes an electrolyte lithium salt, which includes one or more of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate (LiPF6). These lithium salts are readily dissociated, facilitating rapid lithium-ion migration, and the electrolyte system is relatively stable and not easily decomposed, thus improving the cycle performance and fast-charging performance of the battery cells.

[0390] Optionally, the mass content of the electrolyte lithium salt in the electrolyte is 10% to 18%, for example, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, or any combination of two of the above values. When the mass content of the electrolyte lithium salt is within the above range, it is beneficial for the rapid migration of lithium ions, and the electrolyte system is relatively stable and not easily decomposed, which can improve the cycle performance and fast charging performance of the battery cells.

[0391] Optionally, the electrolyte lithium salt includes lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6). When the electrolyte lithium salt includes the above components, it can improve both the cycle performance and fast charging performance of the battery cell.

[0392] Further optionally, the mass content of lithium bis(fluorosulfonyl)imide (LiFSI) in the electrolyte is 4% to 6%, for example, 4%, 4.5%, 5%, 5.5%, 6%, or any combination of two of the above values. When the mass content of lithium bis(fluorosulfonyl)imide (LiFSI) is within the above range, the amount of lithium hexafluorophosphate added is relatively low, which can reduce the acid production of lithium hexafluorophosphate, improve the interfacial stability on the negative electrode side, and help improve the cycle performance of the battery cell.

[0393] Further optionally, the mass content of lithium hexafluorophosphate (LiPF6) in the electrolyte is 8% to 12%, for example, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, or any combination of both or any combination of the above values.

[0394] In the embodiments of this application, the types and contents of inorganic components / electrolyte lithium salts in the electrolyte are known in the art and can be detected using equipment and methods known in the art. For example, the inorganic components / electrolyte lithium salts in the electrolyte can be qualitatively or quantitatively analyzed by referring to standards JY / T 0575-2020 "General Rules for Ion Chromatography Analysis" and GB / T 6040-2019 "General Rules for Infrared Spectroscopy Analysis". In the embodiments of this application, freshly prepared electrolyte can be used as a sample, the free electrolyte of a fresh battery can be used as a sample, or a fully discharged battery cell can be disassembled in reverse (discharged to the discharge cutoff voltage so that the charge state of the battery cell is about 0% SOC), and the free electrolyte obtained from the battery cell can be used as a sample for detection by ion chromatography analysis.

[0395] In the embodiments of this application, the types and contents of organic components in the electrolyte are known in the art and can be detected using equipment and methods known in the art. For example, the organic components of the electrolyte can be qualitatively and quantitatively analyzed by gas chromatography using GB / T 9722-2023 "General Rules for Gas Chromatography of Chemical Reagents".

[0396] In the embodiments of this application, after quantitative and qualitative detection of each component in the electrolyte, each component is classified. Carboxylic acid ester solvents and carbonate solvents (such as ethylene carbonate, propylene carbonate, butene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate) are regarded as components of organic solvents. The mass content of each component is calculated based on the mass of the electrolyte as 100%.

[0397] Carbonate additives (such as vinylene carbonate, fluoroethylene carbonate, etc.), sulfur-containing additives, and lithium salt additives are used as additives in the electrolyte. The mass content of each component is calculated based on the mass of the electrolyte as 100%.

[0398] In some embodiments, the volumetric energy density of the battery cell is between 440 Wh / L and 520 Wh / L, for example, 440 Wh / L, 450 Wh / L, 455 Wh / L, 460 Wh / L, 465 Wh / L, 470 Wh / L, 475 Wh / L, 480 Wh / L, 485 Wh / L, 490 Wh / L, 495 Wh / L, 500 Wh / L, 505 Wh / L, 510 Wh / L, 515 Wh / L, 520 Wh / L, or any range of two of the above values. The volumetric energy density of the battery cell is relatively high.

[0399] like Figure 1 and Figure 2 As shown, in some embodiments, the battery cell 7 may include a housing 20.

[0400] The outer casing 20 can be of various shapes, such as a cylinder or a cuboid. The shape of the outer casing 20 can be determined according to the specific shape of the electrode assembly 10. For example, if the electrode assembly 10 is a cylindrical structure, the outer casing 20 can be a cylindrical structure. If the electrode assembly 10 is a cuboid structure, the outer casing 20 can be a cuboid structure. Optionally, the electrode assembly 10 can be a cuboid structure.

[0401] The outer casing 20 can be made of various materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, etc., and this application embodiment does not impose any special limitations on this. Optionally, the inner wall of the outer casing 20 may also include an insulating layer, which can separate the outer casing 20 from the electrode assembly 10. The material of the insulating layer can be selected from materials commonly used in the art, and is not particularly limited here.

[0402] The electrode assembly 10 housed within the housing 20 may be one or more.

[0403] In some embodiments, the housing 20 includes a housing 21 and an end cap 22, the housing 21 having an opening and the end cap 22 closing the opening, the housing 21 containing the electrode assembly 10 and the electrolyte.

[0404] In some embodiments, the casing 21 is made of one or more materials, including aluminum and stainless steel. Stainless steel is a preferred material because it has high mechanical strength, is not easily deformed, and can improve the reliability and cycle performance of the battery cell. Optionally, when the casing 21 is made of stainless steel, stainless steel is the material with the highest mass percentage in the casing 21.

[0405] Optionally, the shell 21 is a cuboid structure.

[0406] For example, the housing 21 includes a bottom wall 211 and a side wall 212 surrounding the bottom wall 211. The bottom wall 211 and the side wall 212 are connected, and the bottom wall 211 is disposed opposite to the end cap 22.

[0407] Optionally, the thickness of the bottom wall 211 is from 0.6 mm to 1.5 mm, such as 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, or any combination of two of the above values.

[0408] When the thickness of the bottom wall 211 is within the above range, the mechanical strength of the bottom wall 211 is high, which can improve the reliability and cycle performance of the battery cell 7.

[0409] Optionally, the thickness of the sidewall 212 is from 0.2 mm to 1.0 mm, for example, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm or any range of two of the above values.

[0410] When the thickness of the sidewall 212 is within the above range, the sidewall 212 occupies less space, and the internal space of the casing 21 is more, which is beneficial to improving the energy density of the battery cell 7.

[0411] The following explanation will take the electrode assembly 10, which has a stacked structure, as an example.

[0412] The electrode assembly 10 includes a positive electrode 11, a negative electrode 12, and a separator 13 stacked along the thickness direction X of the battery cell 7.

[0413] like Figure 2 and Figure 3 As shown,

[0414] The positive electrode 11 includes a positive electrode tab 111, which can be used to draw out the current from the positive current collector 112 or to introduce the current into the positive current collector 112.

[0415] The negative electrode 12 includes a negative electrode tab 121, which can be used to draw out the current from the negative current collector 122 or to introduce the current into the negative current collector 122.

[0416] In some embodiments, the positive electrode tab 111 is connected to at least one side of the positive electrode current collector 112 along the length direction Z of the battery cell 7.

[0417] like Figure 4 As shown, for example, the positive electrode tab 111 is connected to the positive current collector 112 on one side along the length direction Z of the battery cell 7.

[0418] like Figure 5 As shown, for example, the positive electrode tab 111 is connected to both sides of the positive electrode current collector 112 along the length direction Z of the battery cell 7.

[0419] In some embodiments, the negative electrode tab 121 is connected to at least one side of the negative electrode current collector 122 along the length direction Z of the battery cell 7.

[0420] like Figure 6 As shown, for example, the negative electrode tab 121 is connected to the negative electrode current collector 122 on one side along the length direction Z of the battery cell 7.

[0421] like Figure 7 As shown, for example, the negative electrode tab 121 is connected to both sides of the negative electrode current collector 122 along the length direction Z of the battery cell 7.

[0422] In some embodiments, the positive electrode tab 111 is connected to at least one side of the positive current collector 112 along the length direction Z, and the negative electrode tab 121 is connected to at least one side of the negative current collector 122 along the length direction Z.

[0423] like Figure 8 As shown, when the tab is disposed on at least one side of the current collector along the length direction Z, along the length direction Z of the battery cell 7, the size of the negative electrode active material layer 123 is larger than the size of the positive electrode active material layer 113, and the size difference between the negative electrode active material layer 123 and the positive electrode active material layer 113 is OH1; along the width direction Y of the battery cell 7, the size of the negative electrode active material layer 123 is larger than the size of the positive electrode active material layer 113, and the size difference between the negative electrode active material layer 123 and the positive electrode active material layer 113 is OH2, and OH1 is greater than OH2.

[0424] The negative electrode tab 121 is located on at least one side of the negative electrode current collector 122 along the length direction Z. The current density in the connection area between the negative electrode tab 121 and the negative electrode current collector 122 increases sharply, making it more prone to problems such as lithium plating. However, in the embodiment of this application, OH1 is set to be greater than OH2, which makes the ability of the negative electrode active material layer 123 to receive lithium ions in the length direction Z stronger. In particular, it can improve the ability of the negative electrode active material layer 123 to receive lithium ions in the area near the negative electrode tab 121, reduce the risk of lithium plating, and improve the reliability of the battery cell 7.

[0425] For example, OH1 is 1 mm to 4 mm, such as 1 mm, 1.2 mm, 1.5 mm, 1.8 mm, 2 mm, 2.2 mm, 2.5 mm, 2.8 mm, 3.0 mm, 3.5 mm, 4 mm, or any combination of two of the above values. Along the length direction Z, the negative electrode active material layer 123 extends beyond the positive electrode active material layer 113 on both sides, exceeding OH1 / 2 on each side, that is, half the size of OH1. Figure 8 OH1 / 2 is shown in the figure.

[0426] For example, OH2 is 1mm to 3mm, such as 1mm, 1.2mm, 1.5mm, 1.8mm, 2mm, 2.2mm, 2.5mm, 2.8mm, 3mm, or any combination of two of the above values. Along the width direction Y, the negative electrode active material layer 123 extends beyond the positive electrode active material layer 113 on both sides, exceeding OH2 / 2 on each side, i.e., half the size of OH2. Figure 8 The figure shows OH2 / 2.

[0427] In some embodiments, the dimension of the negative electrode active material layer 123 along the length direction Z of the battery cell 7 is 100 mm to 650 mm, for example, 100 mm, 200 mm, 250 mm, 300 mm, 350 mm, 400 mm, 450 mm, 500 mm, 550 mm, 600 mm, 650 mm, or any range of two of the above values. The length direction Z of the battery cell 7, the length direction of the electrode assembly 10, and the length direction of the negative electrode active material layer 123 are parallel to each other, and the dimension of the negative electrode active material layer 123 along the length direction of the electrode assembly 10 can be understood as the length of the negative electrode active material layer 123. Figure 8 Z2 represents the length of the negative electrode active material layer 123. Figure 8 Z1 represents the length of the positive electrode active material layer 113.

[0428] When the length of the negative electrode active material layer 123 is within the above range, it is beneficial to increase the space occupied by the negative electrode active material, which can balance the volumetric energy density and fast charging performance of the battery cell 7.

[0429] In other embodiments, the positive electrode tab 111 is connected to at least one side of the positive current collector 112 along the width direction Y, and the negative electrode tab 121 is connected to at least one side of the negative current collector 122 along the width direction Y.

[0430] In some embodiments, the battery cell 7 also includes a positive terminal 31, which is disposed on the housing 20 and may be disposed on the housing 21 or the end cap 22.

[0431] The positive terminal 31 is electrically connected to the positive electrode tab 111. Optionally, the positive terminal 31 and the positive electrode tab 111 are welded together. The positive terminal 31 and the positive electrode tab 111 can be connected by an adapter, or they can be connected without an adapter. Optionally, the positive terminal 31 and the positive electrode tab 111 are directly welded together without an adapter, which can reduce the resistance at the connection point, which is beneficial to reducing the overall internal resistance of the battery cell 7 and improving the fast charging performance of the battery cell 7.

[0432] In some embodiments, the battery cell 7 also includes a negative terminal 32, which is disposed on the housing 20, and may be disposed on the housing 21 or the end cap 22.

[0433] The negative terminal 32 is electrically connected to the negative electrode tab 121. Optionally, the negative terminal 32 and the negative electrode tab 121 are welded together. The negative terminal 32 and the negative electrode tab 121 can be connected by an adapter, or they can be connected without an adapter. Optionally, the negative terminal 32 and the negative electrode tab 121 are directly welded together without an adapter, which can reduce the resistance at the connection point, which is beneficial to reducing the overall internal resistance of the battery cell 7 and improving the fast charging performance of the battery cell 7.

[0434] like Figure 9 and Figure 10 As shown, in some embodiments, the positive electrode tab 111 and the negative electrode tab 121 are disposed at the same end along the length direction Z of the battery cell 7. This arrangement helps to reduce the space occupied by the tabs and increase the space occupied by the active material, thereby increasing the volumetric energy density of the battery cell 7.

[0435] Figure 9 In the electrode assembly 10, both ends are provided with a positive electrode tab 111 and a negative electrode tab 121.

[0436] Figure 10 In the electrode assembly 10, a positive electrode tab 111 and a negative electrode tab 121 are provided at one end.

[0437] like Figure 11 As shown, in some other embodiments, the positive electrode tab 111 and the negative electrode tab 121 are disposed at opposite ends along the length direction Z of the battery cell 7.

[0438] like Figure 12 As shown, the battery cell 7 in the embodiments of this application can be assembled into a battery module 6. The number of battery cells 7 contained in the battery module 6 can be one or more, and the specific number can be adjusted according to the application and capacity of the battery module 6.

[0439] If there are multiple battery cells 7, they can be connected in series, parallel, or in a mixed configuration. A mixed configuration means that some battery cells 7 are connected in series while others are connected in parallel. Multiple battery cells 7 can be directly connected in series, parallel, or in a mixed configuration, and then the entire assembly of these battery cells 7 is housed within the housing of the battery module 6. Alternatively, multiple battery cells 7 can first be connected in series, parallel, or in a mixed configuration to form the battery module 6, and then the multiple battery modules 6 can be connected in series, parallel, or in a mixed configuration to form a whole, which is then housed within the housing. Optionally, the battery module 6 may also include a housing with a accommodating space, within which multiple battery cells 7 are housed.

[0440] Multiple battery cells 7 of the battery module 6 can be electrically connected through a busbar to achieve parallel, series, or mixed connection of the multiple battery cells 7 of the battery module 6. There can be one or more busbars, and each busbar is used to electrically connect at least two battery cells 7.

[0441] like Figure 13 As shown, the battery pack 2 may include a housing 5 and a plurality of battery modules 6 disposed in the housing 5. The housing 5 includes a first housing portion 5a and a second housing portion 5b, and the housing 5 has a receiving space 5c. The first housing portion 5a is used to cover the second housing portion 5b and form a closed space for accommodating the battery modules 6. The plurality of battery modules 6 can be arranged in the housing 5 in any manner.

[0442] The first housing portion 5a and the second housing portion 5b overlap each other, and together they define a receiving space 5c for accommodating a single battery cell. The second housing portion 5b can be a hollow structure with one open end, and the first housing portion 5a can be a plate-like structure. The first housing portion 5a covers the open side of the second housing portion 5b to form a housing 5 with the receiving space 5c. Alternatively, both the first housing portion 5a and the second housing portion 5b can be hollow structures with one open side, with the open side of the first housing portion 5a covering the open side of the second housing portion 5b to form a housing 5 with the receiving space 5c. Of course, the first housing portion 5a and the second housing portion 5b can be of various shapes, such as cylinders, cuboids, etc.

[0443] To improve the sealing performance after the first housing part 5a and the second housing part 5b are connected, a sealing element, such as sealant or sealing ring, can also be provided between the first housing part 5a and the second housing part 5b.

[0444] Assuming that the first box section 5a covers the top of the second box section 5b, the first box section 5a can also be called the upper box cover, and the second box section 5b can also be called the lower box.

[0445] The aforementioned battery cells, battery modules, and battery packs are all examples of battery devices.

[0446] Electrical appliances

[0447] The second aspect of this application provides an electrical device, which includes a battery device as described in this application, such as a battery cell, battery module, or battery pack. The battery cell, battery module, or battery pack can be the power source of the electrical device or the energy storage unit of the electrical device. The electrical device can be a vehicle, mobile phone, portable device, laptop computer, ship, spacecraft, electric toy, and power tool, etc. Vehicles can be gasoline-powered vehicles, natural gas-powered vehicles, or new energy vehicles; new energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc.; spacecraft include airplanes, rockets, space shuttles, and spacecraft, etc.; electric toys include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc.; power tools include metal cutting power tools, grinding power tools, assembly power tools, and railway power tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators, and electric planers, etc. This application does not impose any special limitations on the above-described electrical device.

[0448] Electrical devices can be equipped with individual battery cells, battery modules, or battery packs depending on their usage requirements.

[0449] Figure 14 This is a schematic diagram of an example electrical device 1. This electrical device 1 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements of this electrical device 1, a battery pack or battery module can be used.

[0450] The electrical device 1 is equipped with a battery pack 2, which can be located at the bottom, head, or tail of the electrical device 1. The battery pack 2 can be used to supply power to the electrical device 1. For example, the battery pack 2 can serve as the operating power source for the electrical device 1, and can also serve as the driving power source for the electrical device 1, replacing or partially replacing fuel oil or natural gas to provide driving power for the electrical device 1.

[0451] Electrical device 1 may also include controller 3 and motor 4. Controller 3 is used to control battery pack 2 to supply power to motor 4, for example, to meet the power needs of electrical device 1 during startup, navigation and driving.

[0452] Another example of an electrical device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell as their power source.

[0453] Example

[0454] The following embodiments describe the contents disclosed in this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of the embodiments of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0455] Example 1

[0456] (1) Preparation of positive electrode sheet

[0457] The positive electrode includes a positive current collector, a positive conductive layer on the positive current collector, and a positive active material layer. The positive current collector is an aluminum foil with a thickness of 13μm.

[0458] The positive electrode conductive layer on the positive electrode current collector is a film formed by uniformly mixing the positive electrode conductive agent superconducting carbon, the positive electrode binder polyvinylidene fluoride (PVDF), and the solvent N-methylpyrrolidone (NMP), coating it on both sides of the positive electrode current collector, and drying it. The thickness is 1 μm. The mass content of the positive electrode conductive agent in the positive electrode conductive layer is 40%, and the mass content of the positive electrode binder is 60%.

[0459] The positive electrode active material layer comprises a film layer formed by uniformly coating the surface of the positive electrode conductive layer with a positive electrode slurry (solvent being N-methylpyrrolidone NMP) and then drying and cold pressing it. The positive electrode active material layer comprises positive electrode active material, binder polyvinylidene fluoride PVDF, and conductive agent acetylene black in a weight ratio of 97:2:1.

[0460] The positive electrode active material includes lithium iron phosphate, which has a coating layer that coats the surface of the lithium iron phosphate particles. The coating layer includes lithium titanium iron phosphate (Li2FeTi(PO4)3) and carbon elements, with the carbon elements accounting for 1.65% of the mass of the positive electrode active material.

[0461] The single-sided density of the positive electrode active material layer is 272 mg / 1540.25 mm². 2 After the positive electrode is assembled into a battery cell, the compaction density of the positive electrode active material layer at 0% SOC is 2.75 g / cm³. 3 .

[0462] (2) Preparation of negative electrode sheet

[0463] The negative electrode sheet includes a negative current collector, a negative conductive layer on the negative current collector, and a negative active material layer. The negative current collector is a copper foil with a thickness of 5μm.

[0464] The negative electrode conductive layer on the negative electrode current collector is a film formed by uniformly mixing the negative electrode conductive agent superconducting carbon, the negative electrode binder styrene-butadiene rubber SBR, the thickener sodium carboxymethyl cellulose CMC-Na, and the solvent water, coating it on both sides of the negative electrode current collector, and drying it. The thickness is 1μm. The negative electrode conductive agent has a mass content of 35% in the negative electrode conductive layer, the negative electrode binder has a mass content of 60% in the negative electrode conductive layer, and the thickener has a mass content of 5% in the negative electrode conductive layer.

[0465] A first negative electrode slurry is uniformly coated onto the negative electrode conductive layer of the negative electrode current collector copper foil and dried to form a first negative electrode active material layer. A second negative electrode slurry is then coated onto the surface of the dried first negative electrode active material layer and dried to form a second negative electrode active material layer. After cold pressing, a negative electrode sheet is obtained. The thickness ratio of the first negative electrode active material layer to the second dried first negative electrode active material layer is 5:5.

[0466] The negative electrode active material layer includes a first negative electrode active material layer and a second negative electrode active material layer. The first negative electrode active material layer is located on the surface of the negative electrode conductive layer, and the second negative electrode active material layer is located on the surface of the first negative electrode active material layer.

[0467] The first negative electrode active material layer comprises carbon-based material, silicon-carbon material, conductive agent conductive carbon black, binder lithium polyacrylate, styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose in a mass ratio of 89:6:0.8:0.9:2.3:1.

[0468] Silicon-carbon materials consist of a porous carbon framework and silicon within the porous carbon framework. The silicon content in silicon-carbon materials is 52% by mass, and the Dv50 of silicon-carbon materials is 8.5 μm.

[0469] The carbon-based material has a Dv50 of 15.5 μm and includes artificial graphite and a negative electrode coating layer. The carbon content of the negative electrode coating layer is 2.1% by mass.

[0470] The second negative electrode active material layer comprises carbon-based material, silicon-carbon material, conductive agent conductive carbon black, binder lithium polyacrylate, styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose in a mass ratio of 90.9:6:0.6:0.6:0.9:1.

[0471] Silicon-carbon materials consist of a porous carbon framework and silicon within the porous carbon framework. The silicon content in silicon-carbon materials is 52% by mass, and the Dv50 of silicon-carbon materials is 8.5 μm.

[0472] The carbon-based material has a Dv50 of 11.8 μm and includes artificial graphite and a negative electrode coating layer. The carbon content of the negative electrode coating layer is 2.3% by mass.

[0473] The single-sided density of the negative electrode active material layer is 122 mg / 1540.25 mm².2 After the negative electrode sheet is assembled into a battery cell, the compaction density of the negative electrode active material layer at 0% SOC is 1.36 g / cm³. 3 .

[0474] (3) Separating membrane

[0475] The separator membrane includes a base membrane, a first functional layer, and a second functional layer. The base membrane consists of 7μm polyethylene (PE), and the separator membrane has a porosity of 42%.

[0476] The first functional layer is a film layer formed by coating alumina particles and polyvinylidene fluoride binder on both sides of the base film, with a thickness of 2μm and an average particle size of 10nm for the alumina particles.

[0477] The second functional layer is a film formed by coating polyvinylidene fluoride onto the first functional layer, and the thickness of the second functional layer is 1 μm.

[0478] (4) Preparation of electrolyte

[0479] The electrolyte consists of organic solvents, lithium salts, and additives.

[0480] After mixing the components in the organic solvent, lithium salt and additives are added and mixed to form an electrolyte.

[0481] The organic solvents include 40% linear carboxylic acid ester solvent (ethyl acetate) and 40% carbonate solvents (30% ethylene carbonate EC and 10% dimethyl carbonate). The mass content of each component in the organic solvents is calculated based on the mass of the electrolyte.

[0482] Based on the mass of the electrolyte, the total mass content of the additives is 5%, which includes vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl sulfite (ES), and lithium difluorooxalate borate (LiDFOB) in a mass ratio of 3:1.5:0.3:0.2.

[0483] The electrolyte lithium salt comprises 5% by mass of lithium bis(fluorosulfonyl)imide (LiFSI) and 10% by mass of lithium hexafluorophosphate (LiPF6). The mass content of the electrolyte lithium salt is calculated based on the mass of the electrolyte.

[0484] (5) Preparation of battery cells

[0485] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation, thus obtaining an electrode assembly. The electrode assembly is placed in an outer packaging shell, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping, a battery cell is obtained.

[0486] The shell is made of aluminum, with a bottom wall thickness of 1.0 mm and a side wall thickness of 0.6 mm.

[0487] Examples 2-1 to 2-4

[0488] Battery cells were prepared using a method similar to that of Example 1, except that the mass content of silicon in the negative electrode active material layer was adjusted.

[0489] Examples 2-5

[0490] Battery cells were prepared using a method similar to that of Example 1, except that the silicon-based material was changed to silicon oxide (SiO2). x x ranges from 0.5 to 2.

[0491] Comparative Example 1-1 and Comparative Example 1-2

[0492] Battery cells were prepared using a method similar to that of Example 1, except that the mass content of silicon in the negative electrode active material layer was adjusted.

[0493] The negative electrode active material layer in Comparative Example 1-1 does not include silicon-based materials, and the compaction density of the negative electrode active material layer and the compaction density of the positive electrode active material layer were adjusted.

[0494] Performance testing

[0495] 1. Volumetric energy density of a single battery cell

[0496] At 25℃, the battery cell is discharged at a constant current of 0.33C to 2.0V, left to stand for 5 minutes, charged at a constant current of 0.33C to the upper limit cutoff voltage of 3.8V, and then charged at a constant voltage to a current of 0.05C, left to stand for 5 minutes; discharged at a constant current of 0.33C to the discharge cutoff voltage of 2.0V, and the discharge capacity at this time is recorded and the discharge energy E0 is obtained, in Wh; the length, width and height of the battery cell are measured with calipers, and the volume V0 of the battery cell is calculated, in L;

[0497] Volumetric energy density (Wh / L) = Discharge energy E0 / Cell volume (L).

[0498] 2. Cycle performance of individual battery cells

[0499] At 25°C, charge the battery cell to 3.8V at a charging rate of 0.5C, then charge it to 0.05C at a constant voltage of 3.8V, let it stand for 10 minutes, and then discharge it to the discharge cutoff voltage of 3.0V at a discharge rate of 0.33C, and let it stand for 10 minutes. One charge-discharge cycle is one cycle. The test is stopped when the capacity of the battery cell decays to 80% of the nominal capacity. This number is recorded as the number of cycles @ 80% SOH. The more cycles, the longer the cycle life and the better the cycle performance.

[0500] 3. Fast charging time of individual battery cells

[0501] At room temperature, such as 25°C, individual battery cells can be assembled into a battery device, and the required charging and discharging strategies can be controlled by the battery management system for testing.

[0502] The charging process for a single battery cell from 0% to 80% state of charge can be performed as follows:

[0503] Charge from 0% SOC to 5% SOC at a constant current of 7.0C;

[0504] Charge from 5% SOC to 10% SOC at a constant current of 7.0C;

[0505] Charge from 10% SOC to 15% SOC at a constant current of 7.0C;

[0506] Charge from 15% SOC to 20% SOC at a constant current of 7.0C;

[0507] Charge from 20% SOC to 25% SOC at a constant current of 7.0C;

[0508] Charge from 25% SOC to 30% SOC at a constant current of 6.6C;

[0509] Charge from 30% SOC to 35% SOC at a constant current of 6.2C;

[0510] Charge from 35% SOC to 40% SOC at a constant current of 5.7C;

[0511] Charge from 40% SOC to 45% SOC at a constant current of 5.2C;

[0512] Charge from 45% SOC to 50% SOC at a constant current of 4.8C;

[0513] Charge from 50% SOC to 55% SOC at a constant current of 4.6C;

[0514] Charge from 55% SOC to 60% SOC at a constant current of 4.4C;

[0515] Charge from 60% SOC to 65% SOC at a constant current of 4.2C;

[0516] Charge from 65% SOC to 70% SOC at a constant current of 3.9C;

[0517] Charge from 70% SOC to 75% SOC at a constant current of 3.5C;

[0518] Charge from 75% SOC to 80% SOC at a constant current of 3.0C.

[0519] Record the total charging time during the charging process from 10% SOC to 80% SOC.

[0520] The shorter the charging time of a single battery cell, the faster the charging speed, and the better the fast charging performance of the battery cell.

[0521] The test results are shown in Table 1.

[0522] Table 1

[0523]

[0524] The mass content of silicon affects the energy density, cycle performance, and other properties of a single battery cell. For example, increasing the mass content of silicon can effectively improve the capacity of the negative electrode active material layer and increase the energy density of the battery cell, but it may be detrimental to the fast charging performance and cycle performance of the battery cell.

[0525] For example, in Comparative Example 1-1, the negative electrode active material layer does not include silicon-based materials, and its cycle performance and fast charging performance are relatively good; the compaction density of its negative electrode active material layer is 1.22 g / cm³. 3 The compaction density of the positive electrode active material layer is 2.5 g / cm³. 3 Furthermore, the lack of silicon-based materials results in lower capacity and poor volumetric energy density of individual battery cells.

[0526] In Comparative Examples 1-2, the silicon-based material content of the negative electrode active material layer is too high. Although the volumetric energy density of the battery cell is high, the cycle performance and fast charging performance are poor.

[0527] The silicon content in the negative electrode active material layer of Examples 2-1 to 2-4 of this application is within an appropriate range. When combined with an appropriate range of linear polymer alkali metal salts, it can effectively balance the energy density, fast charging performance and cycle performance of the battery cell.

[0528] Various specifications of silicon-based materials are applicable to this application, such as the silicon-carbon material of Example 1, and the silicon oxide of Examples 2-5. Compared with silicon oxide, silicon-carbon materials have a better effect on mitigating the volume expansion of silicon, which is more conducive to balancing the energy density, fast charging performance and cycle performance of battery cells.

[0529] Examples 3-1 to 3-4

[0530] Battery cells were prepared using a method similar to that of Example 1, except that the mass content of the linear polymer alkali metal salt in the negative electrode active material layer was adjusted.

[0531] Examples 4-1 and 4-2

[0532] Battery cells were prepared using a method similar to that of Example 1, except that the mass content of lithium in the linear polymer alkali metal salt was adjusted.

[0533] In Example 4-1, the lithium content was 3% by mass, and in Example 4-2, the lithium content was 7.5% by mass. In Example 1, the lithium content in the linear polymer alkali metal salt was 6% by mass.

[0534] Example 5

[0535] Battery cells were prepared using a method similar to that of Example 1, except that the number-average molecular weight of the linear polymer alkali metal salt was adjusted to 300 kDa. In Example 1, the number-average molecular weight of the linear polymer alkali metal salt was 800 kDa.

[0536] Example 6

[0537] Battery cells were prepared using a method similar to that of Example 1, except that the polydispersity index of the linear polymer alkali metal salt was adjusted to 1.5. In Example 1, the polydispersity index of the linear polymer alkali metal salt was 1.2.

[0538] Examples 7-1 to 7-3

[0539] Battery cells were prepared using a method similar to that of Example 1, except that the mass content of the negative electrode binder in the negative electrode active material layer was adjusted.

[0540] The test results are shown in Table 2.

[0541] Table 2

[0542]

[0543]

[0544] A represents the mass content of the linear polymer alkali-free metal salt in the negative electrode active material layer;

[0545] A1 represents the mass content of the linear polymer alkali-free metal salt in the first negative electrode active material layer;

[0546] A2 represents the mass content of the linear polymer alkali-free metal salt in the second negative electrode active material layer;

[0547] B represents the mass content of the negative electrode binder in the negative electrode active material layer;

[0548] B1 represents the mass content of the negative electrode binder in the first negative electrode active material layer;

[0549] B2 represents the mass content of the negative electrode binder in the second negative electrode active material layer.

[0550] In Comparative Example 2-1, during the charging and discharging process of a single battery cell, the silicon-based material undergoes volume expansion or contraction, causing the SEI film on the surface of the silicon-based material to rupture repeatedly, exposing the surface of the silicon-based material, exacerbating interfacial side reactions, and deteriorating cycle performance and fast charging performance.

[0551] The linear polymer alkali metal salt content in the negative electrode active material layer of Comparative Example 2-2 is too high. Although it can effectively alleviate the volume expansion of silicon-based materials, its high content reduces the mass ratio of the negative electrode active material and decreases the capacity of the negative electrode active material layer. Furthermore, the excessive content of linear polymer alkali metal salt may increase the lithium ion migration resistance in the negative electrode active material layer, increase the internal resistance, deteriorate the kinetic performance, and hinder the fast charging of the battery cell. The deterioration of kinetic performance increases the risk of lithium plating on the negative electrode sheet, resulting in a decrease in the cycle life of the battery cell.

[0552] The negative electrode active material layer in this application embodiment includes a linear polymer alkali metal salt, which can alleviate the volume expansion of silicon-based materials; moreover, the main chain structure of the linear polymer without alkali metal salt is a linear structure, which can effectively encapsulate silicon-based materials, further alleviating the degree of volume expansion of silicon-based materials, reducing the damage of volume expansion of silicon-based materials to SEI film, and improving cycle performance.

[0553] As the mass content of linear polymer alkali metal salt increases, it can better constrain the volume expansion of silicon-based materials, and the cycle performance is further improved. Moreover, linear polymer alkali metal salt can improve the lithium-ion migration rate. However, the increase in the mass content of linear polymer alkali metal salt will also lead to a sharp increase in electrode resistance, deterioration of kinetic performance, which is not conducive to fast charging, and will reduce electrode capacity and energy density of battery cells. The mass content of linear polymer alkali metal salt in Examples 3-1 to 3-4 is within an appropriate range, which can balance the cycle performance, energy density and fast charging performance of battery cells.

[0554] The mass content of lithium in linear polymer alkali metal salts has a certain influence on lithium-ion transport. In Examples 4-1 and 4-2, the increase in the mass content of lithium is beneficial to improving the fast charging and cycle performance of the battery cells.

[0555] When the number-average molecular weight of the linear polymer alkali metal salts in Examples 1 and 5 is within an appropriate range, the linear polymer alkali metal salts have appropriate viscosity. On the one hand, this can increase the compactness of each particle in the negative electrode active material layer and reduce the contact internal resistance. On the other hand, it can effectively encapsulate the silicon-based material, alleviate the volume expansion of the silicon-based material, and improve the cycle performance and fast charging performance of the battery cell.

[0556] When the polydispersity coefficient of the linear polymer alkali metal salts in Examples 1 and 6 is within the above range, the molecular weight distribution of the linear polymer alkali metal salts is more concentrated, the performance of the linear polymer alkali metal salts is more uniform, and they can more effectively improve the performance of the negative electrode active material layer, which is beneficial to improving the cycle performance and fast charging performance of the battery cell.

[0557] As the total mass content of linear polymer alkali metal salt and negative electrode binder in the negative electrode active material layer increases, the bonding force between the negative electrode active material layer and the negative electrode current collector can be increased; however, the internal resistance of the negative electrode active material layer increases, the kinetic performance deteriorates, the risk of lithium plating on the negative electrode increases, and the cycle life of the battery cell decreases.

[0558] In Examples 7-1 to 7-3, the total mass content of the linear polymer alkali metal salt and the negative electrode binder in the highly active material layer is within an appropriate range, which can balance the energy density, cycle performance, and fast charging performance of the battery cell; specifically,

[0559] The total mass content of linear polymer alkali metal salt and negative electrode binder in the first negative electrode active material layer is relatively high, while the total mass content of linear polymer alkali metal salt and negative electrode binder in the second negative electrode active material layer is relatively low. In other words, the total mass content of linear polymer alkali metal salt and negative electrode binder in the first negative electrode active material layer is greater than or equal to the total mass content of linear polymer alkali metal salt and negative electrode binder in the second negative electrode active material layer. This is beneficial to improve the bonding stability of each film layer of the negative electrode sheet, reduce the risk of layer peeling, and take into account the energy density, cycle performance and fast charging performance of the battery cell.

[0560] The application also applies to cases where the negative electrode active material layer is a single-layer film. The mass content of the linear polymer alkali metal salt is within the range of this application, which can also take into account the energy density, cycle performance and fast charging performance of the battery cell.

[0561] Example 8

[0562] Battery cells were prepared using a method similar to that of Example 1. The difference from Example 1 was that the negative electrode active material layer was adjusted, and the conductive agent included carbon nanotubes and conductive carbon black in a mass ratio of 1:1.

[0563] The test results are shown in Table 3.

[0564] Table 3

[0565]

[0566] Compared to Example 1, which did not add carbon nanotubes to the negative electrode active material layer, Example 8 added carbon nanotubes. The carbon nanotubes have a linear structure and are conductive. The linear structure of the carbon nanotubes can wrap around the surface of the silicon-based material, which can alleviate the volume expansion of the silicon-based material and improve the fast charging performance and cycle performance of the battery cell. However, if too much carbon nanotubes are added, it will reduce the capacity of the negative electrode active material layer and reduce the energy density of the battery cell.

[0567] The carbon nanotube content in Example 8 is within an appropriate range, which can more effectively balance the energy density, cycle performance and fast charging performance of the battery cell.

[0568] In Example 8, the length of the carbon nanotubes is within a certain range. Increasing the length improves the wrapping performance of silicon-based materials, thus more effectively improving the fast charging and cycle performance of battery cells. However, if the carbon nanotubes are too long, the wrapping effect will not be further improved, and the cost will increase too much, making them unsuitable for production.

[0569] Examples 9-1 to 9-4

[0570] Battery cells were prepared using a method similar to that in Example 1. The difference from Example 1 was that the mass content of carbonate additives in the electrolyte was adjusted. As the mass content of carbonate additives increased, the mass content of dimethyl carbonate was correspondingly decreased; and as the mass content of carbonate additives decreased, the mass content of dimethyl carbonate was correspondingly increased.

[0571] For example, in Example 9-1, the mass content of carbonate additives is 0.5%, then the mass content of dimethyl carbonate is 14%, and the contents of other components remain basically unchanged.

[0572] For example, in Example 9-2, the mass content of carbonate additives is 5.0%, then the mass content of dimethyl carbonate is 9.5%, and the contents of other components remain basically unchanged.

[0573] For example, in Examples 9-3, the mass content of carbonate additives is 6.5%, then the mass content of dimethyl carbonate is 8%, and the contents of other components remain basically unchanged.

[0574] For example, in Examples 9-4, the mass content of carbonate additives is 8.0%, then the mass content of dimethyl carbonate is 6.5%, and the contents of other components remain basically unchanged.

[0575] Example 9-Z1 is a freshly prepared electrolyte composition. After being assembled into a battery cell and formed, the electrolyte composition obtained by testing is the same as that of Example 9-1.

[0576] In the freshly prepared electrolyte of Example 9-Z1:

[0577] The organic solvents include 39% linear carboxylic acid ester solvent (ethyl acetate) and 43% carbonate solvents (29.4% ethylene carbonate EC and 13.6% dimethyl carbonate). The mass content of each component in the organic solvents is calculated based on the mass of the electrolyte.

[0578] Based on the mass of the electrolyte, the total mass content of the additives is 3.3%, which includes vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl sulfite (ES), and lithium difluorooxalate borate (LiDFOB) in a mass ratio of 1.5:0.5:1:0.3.

[0579] The lithium salts consist of lithium bis(fluorosulfonyl)imide (LiFSI) at a mass content of 4.9% and lithium hexafluorophosphate (LiPF6) at a mass content of 9.8%, with the mass content of the lithium salts calculated based on the mass of the electrolyte.

[0580] Examples 9-Z4 are freshly prepared electrolyte components. After being assembled into battery cells and formed, the electrolyte components obtained by testing are the same as those in Examples 9-4.

[0581] In the freshly prepared electrolyte of Examples 9-Z4:

[0582] The organic solvents include 38.9% linear carboxylic acid ester solvent (ethyl acetate) and 35.3% carbonate solvents (29% ethylene carbonate EC and 6.3% dimethyl carbonate). The mass content of each component in the organic solvents is calculated based on the mass of the electrolyte.

[0583] Based on the mass of the electrolyte, the total mass content of the additives is 11.3%, which includes vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl sulfite (ES), and lithium difluorooxalate borate (LiDFOB) in a mass ratio of 7.5:2.5:1:0.3.

[0584] The lithium salts consist of lithium bis(fluorosulfonyl)imide (LiFSI) at a mass content of 4.8% and lithium hexafluorophosphate (LiPF6) at a mass content of 9.7%, with the mass content of the lithium salts calculated based on the mass of the electrolyte.

[0585] The test results are shown in Table 4.

[0586] Table 4

[0587]

[0588] Carbonate additives can form a dense and elastic SEI film on the negative electrode side surface, effectively mitigating the volume expansion of silicon-based materials;

[0589] In contrast, the carbonate additives in Comparative Example 3-1 had too low a mass content, resulting in a poor-performing SEI film that was not conducive to mitigating the volume expansion of silicon-based materials. Furthermore, the interfacial side reactions were more severe, which deteriorated the cycle performance of the battery cells.

[0590] The carbonate additives in Comparative Example 3-2 have an excessively high mass content, which can effectively alleviate the volume expansion of silicon-based materials and improve the cycle performance of battery cells; however, the resulting SEI film has a high impedance, which is not conducive to fast charging.

[0591] In Table 4, the electrolyte composition of Examples 1, 9-1, 9-2, 9-3, and 9-4 is the result obtained from the test of free electrolyte after disassembling the battery cells.

[0592] The carbonate additives in Examples 9-1 to 9-4 of this application are within an appropriate range in terms of mass content, which can improve both the cycle performance and fast charging performance of the battery cells.

[0593] Although this application has been described with reference to preferred embodiments, various modifications can be made thereto and components can be replaced with equivalents without departing from the scope of this application. In particular, the technical features mentioned in the various embodiments can be combined in any manner as long as there is no structural conflict. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A battery cell, comprising an electrode assembly, the electrode assembly including a positive electrode, a separator, and a negative electrode, the positive electrode including a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, and the negative electrode including a negative current collector and a negative active material layer disposed on at least one side of the negative current collector. in, The positive electrode active material layer includes a lithium phosphate with an olivine structure; The negative electrode active material layer comprises a linear polymer alkali metal salt, a silicon-based material, and a carbon-based material. The linear polymer alkali metal salt has a mass content of 0.3% to 2% in the negative electrode active material layer, and the silicon element in the silicon-based material has a mass content of 0.5% to 5% in the negative electrode active material layer.

2. The battery cell according to claim 1, wherein, The linear polymer alkali metal salt has a mass content of 0.5% to 2% in the negative electrode active material layer.

3. The battery cell according to claim 1 or 2, wherein, The linear polymer alkali metal salt has a mass content of 0.7% to 1.3% in the negative electrode active material layer.

4. The battery cell according to any one of claims 1 to 3, wherein, The alkali metal element in the linear polymer alkali metal salt has a mass content of 3% to 7.5%; and / or The alkali metal element of the linear polymer alkali metal salt includes one or more elements such as lithium, sodium, and potassium.

5. The battery cell according to any one of claims 1 to 4, wherein, The linear polymer alkali metal salt has a number-average molecular weight of 3 kDa to 1000 kDa; and / or The polydispersity index of the linear polymer alkali metal salt is 1 to 1.

5.

6. The battery cell according to any one of claims 1 to 5, wherein, The linear polymer alkali metal salt includes one or more of polyacrylate alkali metal salts and polymethacrylate alkali metal salts.

7. The battery cell according to any one of claims 1 to 6, wherein, The negative electrode active material layer also includes a negative electrode binder. The negative electrode binder includes one or more of styrene-butadiene rubber, water-soluble unsaturated resin, water-based acrylic resin, polyvinyl alcohol, sodium alginate, and carboxymethyl chitosan; and / or The negative electrode binder has a mass content of 0.5% to 3.5% in the negative electrode active material layer.

8. The battery cell according to any one of claims 1 to 7, wherein, The negative electrode active material layer further includes carbon nanotubes, and the mass content of the carbon nanotubes in the negative electrode active material layer is from 0.01% to 1%.

9. The battery cell according to claim 8, wherein, The carbon nanotubes have a length of 1 μm to 5 μm; and / or The carbon nanotubes include one or more types of single-walled carbon nanotubes and multi-walled carbon nanotubes.

10. The battery cell according to any one of claims 1 to 9, wherein, The silicon content of the silicon-based material in the negative electrode active material layer is 0.7% to 3.5% by mass.

11. The battery cell according to any one of claims 1 to 10, wherein, The silicon-based materials include one or more of elemental silicon, silicon-carbon materials, silicon-oxygen materials, silicon-nitrogen materials, and silicon alloys.

12. The battery cell according to claim 11, wherein, The silicon-based materials include one or more of silicon-carbon materials, silicon-oxygen materials, silicon-nitrogen materials, and silicon alloys.

13. The battery cell according to claim 12, wherein, Based on the total mass of the silicon-based material, the silicon element content is 40% to 80% by mass; and / or The volume average particle size Dv50 of the silicon-based material is 3.0 μm to 10 μm; and / or The specific surface area of ​​the silicon-based material is 1m². 2 / g to 3.6m 2 / g; and / or The silicon-based material has a powder compaction density of 0.7 g / cm³ at 25000 N. 3 Up to 1.2 g / cm 3 .

14. The battery cell according to any one of claims 1 to 13, wherein, The carbon-based material includes graphite bulk particles and a negative electrode coating layer covering the surface of the graphite bulk particles. The graphite bulk particles include secondary particles, and the negative electrode coating layer includes carbon elements.

15. The battery cell according to claim 14, wherein, The graphite bulk particles include at least one of artificial graphite and natural graphite.

16. The battery cell according to claim 14 or 15, wherein, Based on the total mass of the carbon-based material, the carbon content of the negative electrode coating layer is 2% to 5% by mass.

17. The battery cell according to any one of claims 1 to 16, wherein, The negative electrode active material layer includes: A first negative electrode active material layer is disposed on the negative electrode current collector; The second negative electrode active material layer is disposed on the side of the first negative electrode active material layer away from the negative electrode current collector. Both the first negative electrode active material layer and the second negative electrode active material layer comprise carbon-based materials, and at least one of the first negative electrode active material layer and the second negative electrode active material layer comprises silicon-based materials.

18. The battery cell according to claim 17, wherein, The volume average particle size Dv50 of the carbon-based material in the first negative electrode active material layer is greater than or equal to the volume average particle size Dv50 of the carbon-based material in the second negative electrode active material layer.

19. The battery cell according to claim 17 or 18, wherein, The volume average particle size Dv50 of the carbon-based material in the first negative electrode active material layer is 10 μm to 20 μm; and / or The volume average particle size Dv50 of the carbon-based material in the second negative electrode active material layer is 9.5 μm to 14.5 μm.

20. The battery cell according to any one of claims 17 to 19, wherein, The mass content of the linear polymer alkali metal salt in the first negative electrode active material layer is greater than or equal to the mass content of the linear polymer alkali metal salt in the second negative electrode active material layer.

21. The battery cell according to claim 20, wherein, The linear polymer alkali metal salt in the first negative electrode active material layer has a mass content of 0.3% to 2.5%; and / or The linear polymer alkali metal salt in the second negative electrode active material layer has a mass content of 0.2% to 1.5%.

22. The battery cell according to claim 20 or 21, wherein, The mass content of the linear polymer alkali metal salt in the first negative electrode active material layer is A1%. The first negative electrode active material layer includes a negative electrode binder, which includes one or more of styrene-butadiene rubber, water-soluble unsaturated resin, water-based acrylic resin, polyvinyl alcohol, sodium alginate and carboxymethyl chitosan. The mass content of the negative electrode binder in the first negative electrode active material layer is B1%. The mass content of the linear polymer alkali metal salt in the second negative electrode active material layer is A2%. The second negative electrode active material layer includes a negative electrode binder, which comprises one or more of styrene-butadiene rubber, water-soluble unsaturated resin, water-based acrylic resin, polyvinyl alcohol, sodium alginate, and carboxymethyl chitosan. The mass content of the negative electrode binder in the second negative electrode active material layer is B2%. Where A1% + B1% ≥ A2% + B2%.

23. The battery cell according to claim 21 or 22, wherein, A1% + B1% is 0.5% to 3.5%; and / or A2% + B2% is 0.5% to 2.5%.

24. The battery cell according to any one of claims 17 to 23, wherein, The thickness ratio of the first negative electrode active material layer to the second negative electrode active material layer is 2:8 to 6:

4.

25. The battery cell according to claim 24, wherein, The thickness ratio of the first negative electrode active material layer to the second negative electrode active material layer is 3:7 to 5:

5.

26. The battery cell according to any one of claims 1 to 25, wherein, The negative electrode sheet further includes a negative electrode conductive layer, which is located between the negative electrode current collector and the negative electrode active material layer. The negative electrode conductive layer includes a negative electrode conductive agent, which includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers; and / or The negative electrode conductive layer includes a negative electrode binder, which includes one or more of styrene-butadiene rubber, water-soluble unsaturated resin, water-based acrylic resin, polyvinyl alcohol, sodium alginate, and carboxymethyl chitosan.

27. The battery cell according to claim 26, wherein, The thickness of the negative electrode conductive layer is 0.5 μm to 2 μm.

28. The battery cell according to any one of claims 1 to 27, wherein the compaction density of the negative electrode active material layer is 1.25 g / cm³. 3 Up to 1.65 g / cm 3 ; and / or The single-sided density of the negative electrode active material layer is 80 mg / 1540.25 mm². 2 Up to 160mg / 1540.25mm 2 .

29. The battery cell according to any one of claims 1 to 28, wherein, The compaction density of the positive electrode active material layer is 2.60 g / cm³. 3 Up to 2.85 g / cm 3 ; and / or The single-sided density of the positive electrode active material layer is 220 mg / 1540.25 mm². 2 Up to 370mg / 1540.25mm 2 .

30. The battery cell according to any one of claims 1 to 29, wherein, The lithium-containing phosphate includes: Phosphate particles, and A positive electrode coating layer is located on at least a portion of the surface of the phosphate particles, and the positive electrode coating layer contains carbon.

31. The battery cell according to claim 30, wherein, The phosphate particles include one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium nickel phosphate, and lithium cobalt phosphate.

32. The battery cell according to any one of claims 1 to 31, wherein the battery cell comprises an electrolyte, the electrolyte comprising a carbonate additive, and the carbonate additive comprising 0.5% to 10% by mass in the electrolyte. The carbonate additives include at least one of vinylene carbonate and ethylene carbonate derivatives, wherein the ethylene carbonate derivatives include compounds represented by formula A. In Formula A, Q1, Q2, Q3 and Q4 each independently include any one of a hydrogen atom, a halogen atom, a C1 to C5 alkyl group, or a C1 to C5 haloalkyl group, and at least one of Q1, Q2, Q3 and Q4 includes a halogen atom, a C1 to C5 alkyl group, or a C1 to C5 haloalkyl group.

33. The battery cell according to claim 32, wherein, The carbonate additive is present in the electrolyte at a mass content of 2% to 10%.

34. The battery cell according to claim 32, wherein, The carbonate additive is present in the electrolyte at a mass content of 0.5% to 8%.

35. The battery cell according to claim 34, wherein, The carbonate additive is present in the electrolyte at a mass content of 1% to 6%.

36. The battery cell according to any one of claims 32 to 35, wherein, The ethylene carbonate derivatives include one or more of fluoroethylene carbonate, difluoroethylene carbonate, and trifluoromethylethylene carbonate.

37. The battery cell according to any one of claims 32 to 36, wherein, The electrolyte further includes sulfur-containing additives, which include one or more of vinyl sulfate, vinyl disulfate, butenyl sulfite, 1,3-propanesulfonyl lactone, vinyl sulfite, and methylene disulfonate; and / or The electrolyte also includes lithium salt additives, which include one or more of lithium difluorophosphate, lithium difluorooxalate borate, lithium tetrafluoroborate, and lithium dioxalate borate.

38. The battery cell according to claim 37, wherein, The sulfur-containing additive has a mass content of 0.3% to 2% in the electrolyte; and / or The lithium salt additive has a mass content of 0.1% to 3% in the electrolyte.

39. The battery cell according to any one of claims 32 to 38, wherein, The electrolyte includes a carboxylic acid ester solvent, and the mass content of the carboxylic acid ester solvent in the electrolyte is 10% to 60%.

40. The battery cell according to claim 39, wherein, The carboxylic acid ester solvents include compounds represented by Formula I. In formula I, R1 includes a hydrogen atom, a C1 to C5 alkyl group, or a C1 to C5 haloalkyl group. R2 includes C1 to C5 alkyl or C1 to C5 haloalkyl.

41. The battery cell according to claim 40, wherein, The carboxylic acid ester solvents include one or more of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, methyl butyrate, and ethyl butyrate.

42. The battery cell according to any one of claims 32 to 41, wherein, The electrolyte also includes a carbonate solvent, wherein the carbonate solvent comprises 20% to 70% by mass in the electrolyte.

43. The battery cell according to claim 42, wherein, The carbonate solvents include one or more of ethylene carbonate, propylene carbonate, butene carbonate, dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate.

44. The battery cell according to any one of claims 32 to 43, wherein, The electrolyte also includes an electrolyte lithium salt, wherein the electrolyte lithium salt has a mass content of 10% to 18% in the electrolyte.

45. The battery cell according to claim 44, wherein, The electrolyte lithium salt includes lithium difluorosulfonylimide and lithium hexafluorophosphate.

46. ​​The battery cell according to claim 45, wherein, The lithium difluorosulfonylimide has a mass content of 4% to 6% in the electrolyte.

47. The battery cell according to any one of claims 1 to 46, wherein, The volumetric energy density of the battery cell is between 440Wh / L and 520Wh / L.

48. A battery device comprising a battery cell as claimed in any one of claims 1 to 47.

49. An electrical device comprising the battery device as described in claim 48.